Method for manufacturing plate-shaped molded article

通过在注射成型过程中精细控制模具表面温度,解决了板状成型品翘曲和外观不良的问题,实现了更高质量的成型品。

CN119427637APending Publication Date: 2025-02-14ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 29 Cites 0 Cited by

Patent Information

Application Number
CN202411061052.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-04
Filing Date
2024-08-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When manufacturing plate-shaped molded products with fine convex shapes, the prior art is difficult to effectively suppress warping and poor appearance of the molded products, especially when the projection area is large.

Method used

By controlling the surface temperatures of the mold fine convex shape and the surface side opposite to the plane side during injection molding within an appropriate temperature range, the specific method includes setting the maximum temperature of the first mold to (glass transition temperature + 40)°C~ (Glass transition temperature +70)℃, and the temperature of the second mold is set to (first mold temperature -90)℃~ (first mold temperature -65)℃.

Benefits of technology

It effectively reduces yellowing, poor appearance and warping of the molded product, and improves the optical characteristics and appearance quality of the molded product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119427637A_ABST
    Figure CN119427637A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a method for producing a plate-shaped molded article having a fine convex shape on one main surface and having a large projected area on the main surface, wherein yellowing, appearance defects, and warpage of the molded article can be reduced. The present invention is a method for producing a plate-like molded article comprising a methacrylic resin composition having a glass transition temperature (Tg) of 115-160 DEG C and a melt viscosity of 20-235 Pa.sec under the conditions of 270 DEG C and 1000 sec <-1 >, the plate-like molded article being configured from a single resin composition without having an adhesive interface, and the sheet-like molded article being characterized in that: the sheet-like molded article contains a methacrylic resin composition having a glass transition temperature (Tg) of 115-160 DEG C and a melt viscosity of 20-235 Pa.sec under the conditions of 270 DEG C and 1000 sec <-1 >; one main surface (first main surface) of the plate-shaped molded article has a plurality of fine convex shapes, the other main surface (second main surface) is a flat surface, the height a of the convex shapes is 0.5-600 [mu] m, the ratio b / a of the pitch b to the height a of the convex shapes is 0.1-2.0, the projected area of the first main surface is 225 cm2 or more, and the projected area of the second main surface is 225 cm2 or more. The manufacturing method includes performing injection molding using a first mold on the first main surface side and a second mold on the second main surface side, the maximum temperature Tmax of the first mold being (Tg + 40) DEG C to (Tg + 70) DEG C, and the temperature of the second mold being (Tmax-90) DEG C to (Tmax-65) DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a plate-shaped molded product having a fine convex shape on one main surface. Background Art

[0002] Conventionally, in the molding of injection molded products having fine concavo-convex shapes, an injection molding method is used, which is characterized in that the entire surface of the mold cavity in contact with the molded product is preheated to a set value above the softening temperature of the resin, and the set value is controlled to be maintained during the injection process. When switching to the cooling process, the heating is completed and the mold is cooled. In this injection molding method, by heating the mold cavity surface to a set value above the softening temperature of the resin before the injection process starts, molding defects such as reduced residual stress, deformation, cracks, and birefringence degradation can be solved (for example, Patent Documents 1 to 6).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent document 1: Japanese Patent Application Laid-Open No. 10-80940.

[0006] Patent document 2: Japanese Patent Application Laid-Open No. 10-80938.

[0007] Patent document 3: Japanese Patent Application Laid-Open No. 11-58476.

[0008] Patent document 4: Japanese Patent Application Laid-Open No. 63-95919.

[0009] Patent document 5: Japanese Patent Application Publication No. 2010-264703.

[0010] Patent document 6: Japanese Patent Application Publication No. 2023-013970. Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, when a mold having a mechanism for heating and cooling only the fine shape imparting surface of the mold is used, a temperature difference occurs between the imparting surface side and the flat surface side opposite thereto, and therefore, the molded product often warps during the cooling process. In particular, when the molded product is used for optical purposes, there is a problem that the shape or warping of the molded product adversely affects the optical characteristics.

[0013] The following method is reported in the above-mentioned patent document 6: when manufacturing a plate-shaped molded product having a fine convex shape on one main surface, the cavity surface is heated to above the load deflection temperature by a heat transfer heating line near the cavity surface, and then a mold is used in a water-cooled manner to control the temperature of the mold surface forming the fine convex shape and the mold surface opposite thereto, while controlling the poor appearance and warping of the molded product. However, in the above-mentioned patent document 6, only molded products with a main surface having a fine convex shape of 90 mm in length and 90 mm in width are studied. When the size (projected area) of the main surface having a fine convex shape becomes larger, poor transfer of the fine convex shape or yellowing of the molded product sometimes occurs near the end of the flow, and there is a problem that a molded product with a good appearance cannot be obtained. In particular, when a molded product with a large projected area of ​​the main surface having a fine convex shape is molded using a resin with a high melt viscosity, there is a significant tendency for poor transfer of the fine convex shape. Furthermore, the present inventors have found through studies that when the projected area of ​​the main surface having a fine convex shape increases, even if the mold temperature is controlled within the range described in Patent Document 6, warping of the molded product may not be sufficiently suppressed.

[0014] The present invention has been completed in view of the above-mentioned problems, and its purpose is to provide a method for manufacturing a plate-like molded product, which can reduce yellowing, poor appearance and warping of the molded product even if the plate-like molded product has a fine convex shape on one main surface and the projected area of ​​the main surface is large.

[0015] Means for solving problems

[0016] The present inventors have studied a method for manufacturing an injection molding product that does not have poor appearance or warping even when the product has a fine convex shape on one main surface and the projection area of ​​the main surface is large. As a result, they found that the above-mentioned problems can be solved by controlling the surface temperature of the fine convex shape shaping surface side and the flat surface side opposite to the mold during injection molding within an appropriate temperature range, thereby completing the present invention.

[0017] That is, the present invention is as follows.

[0018] [1] A method for producing a plate-shaped molded product, characterized in that the plate-shaped molded product comprises a glass transition temperature (Tg) of 115 to 160°C, a melt viscosity of 270°C, and a viscosity of 1000 sec -1 The methacrylic resin composition has a temperature of 20 to 235 Pa·sec under the condition of , wherein the plate-shaped molded product has no bonding interface and is composed of a single resin composition,

[0019] One main surface (first main surface) of the plate-shaped molded product has a plurality of fine convex shapes, and the other main surface (second main surface) is a flat surface.

[0020] The height a of the convex shape is 0.5 to 700 μm, and the ratio b / a of the pitch b of the convex shape to the height a of the convex shape is 0.1 to 2.0.

[0021] The projected area of ​​the first main surface of the plate-shaped molded product is 225 cm 2 above,

[0022] The manufacturing method includes performing injection molding using a first mold forming one side of the first main surface and a second mold forming one side of the second main surface, setting the maximum temperature Tmax of the first mold to (Tg+40)°C to (Tg+70)°C, and setting the temperature of the second mold to (Tmax-90)°C to (Tmax-65)°C.

[0023] [2] The method for producing a plate-shaped molded article according to [1], wherein the methacrylic resin composition has a tensile elongation at break of 1.2% or more.

[0024] [3] The method for manufacturing a plate-shaped molded product according to [1] or [2], wherein the first mold is heated and then cooled to set the minimum temperature Tmin of the first mold to (Tg-75)°C to (Tg-45)°C.

[0025] [4] A method for manufacturing a plate-like molded product as described in any one of [1] to [3], wherein after the first mold is heated and then cooled, the heating rate of the surface temperature of the first mold is set to 1 to 10°C / second, and the cooling rate is set to 0.5 to 10°C / second.

[0026] Effects of the Invention

[0027] According to the present invention, it is possible to produce a plate-shaped molded product having fine convex shapes on one main surface, in which yellowing, appearance defects and warping of the molded product are reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a diagram showing an example (corresponding to Examples 1 to 6) of the plate-like molded product according to the present embodiment. Figure 1 (A) represents a top view (plan view) when viewed from above with the first main surface having a convex shape as the upper surface, Figure 1 (B) shows a side view.

[0029] Figure 2 This is a partial cross-sectional view showing an example (triangular pyramid) of the convex shape of the plate-like molded product according to the present embodiment.

[0030] Figure 3 It means Figure 1A diagram showing an example of a plate-like molded product according to a different embodiment of the present invention (corresponding to Example 7). Figure 3 (A) represents a top view (plan view) when viewed from above with the first main surface having a convex shape as the upper surface, Figure 3 (B) represents a side view, Figure 3 (C) is a perspective view showing a convex shape when viewed from obliquely above.

[0031] Figure 4 It means Figure 2 A partial cross-sectional view of an example (quadrangular pyramid trapezoid) of a convex shape of a plate-like molded product according to another embodiment of the present invention.

[0032] Figure 5 It is a diagram showing the optical path when the plate-like molded products obtained in Examples and Comparative Examples are used as light direction converting elements.

[0033] Figure 6 This is a diagram showing the arrangement of equipment used to evaluate the characteristics of the plate-like molded products obtained in Examples and Comparative Examples when used as light direction converting elements.

[0034] Figure 7 Observed from the X-axis direction Figure 6 Top view of the USAF target 7 used in the test.

[0035] The description of the reference numerals is as follows:

[0036] 1, 2: Plate shaped products;

[0037] 11, 21: One main surface (first main surface) having a fine convex shape;

[0038] 12, 22: the other main surface (second main surface) on which fine convex shapes are not formed;

[0039] 13, 23: Areas with fine convex shapes are formed;

[0040] 14, 24: convex shape;

[0041] 15a, 15b, 15c, 15d: measurement points of warpage;

[0042] 5: LED light source;

[0043] 6: Frosted diffuser plate;

[0044] 7: USAF target;

[0045] 71: Through area;

[0046] 72: shading area;

[0047] 8: Plate shaped products;

[0048] 81: incident surface;

[0049] 82: Bottom;

[0050] 83, 84: inclined plane;

[0051] 9: SLR camera. DETAILED DESCRIPTION

[0052] Hereinafter, an embodiment of the present invention (hereinafter referred to as “the present embodiment”) will be described in detail, but the present invention is not limited to the following description and can be implemented with various modifications within the scope of the gist thereof.

[0053] (Method for producing plate-shaped molded product)

[0054] The method for manufacturing a plate-like molded product of the present embodiment is a method for manufacturing a plate-like molded product (hereinafter, also referred to as a "molded product") containing a methacrylic resin composition described later, characterized in that the manufacturing method includes performing injection molding using a first mold on one side forming a first main surface (a main surface having a plurality of fine convex shapes) of the plate-like molded product and a second mold on one side forming a second main surface (a main surface that is a plane) of the plate-like molded product, setting the maximum temperature Tmax of the first mold to (Tg+40)°C to (Tg+70)°C (Tg is the glass transition temperature of the methacrylic resin composition), and setting the temperature of the second mold to (Tmax-90)°C to (Tmax-65)°C.

[0055] The following describes detailed conditions of injection molding in the method for producing a plate-shaped molded product according to the present embodiment.

[0056] In the present embodiment, the temperature setting from the nozzle tip to the center of the injection molding machine barrel is set to (Tg+120)°C to (Tg+180)°C relative to the glass transition temperature Tg of the methacrylic resin composition used, so that the molten resin flows sufficiently and molding can be performed while suppressing the degradation caused by the thermal decomposition of the resin. It is preferably (Tg+125)°C to (Tg+170)°C, more preferably (Tg+130)°C to (Tg+165)°C, and further preferably (Tg+130)°C to (Tg+160)°C. If the temperature during molding is within the above range, the fluidity can be improved while suppressing the thermal decomposition of the resin, and therefore, there is a tendency to easily obtain a plate-shaped molded product with a good transfer rate of the color tone and fine shape of the molded product.

[0057] In this embodiment, in order to improve the transferability (molding property) of the fine convex shape, the maximum temperature Tmax of the first mold when injecting the resin into the mold is controlled to a temperature range of (Tg+40)°C to (Tg+70)°C. Preferably, it is (Tg+45)°C to (Tg+65)°C, and more preferably, it is (Tg+50)°C to (Tg+60)°C. If Tmax is (Tg+70)°C or less, there is a tendency for good transferability and demolding properties. On the other hand, if Tmax is (Tg+40)°C or more, there is a tendency for good transferability.

[0058] In the present embodiment, when the maximum temperature of the first mold when injecting the resin into the mold is set to Tmax, the temperature of the second mold is set to (Tmax-90)°C to (Tmax-65)°C. It is preferably (Tmax-85)°C to (Tmax-70)°C, and particularly preferably (Tmax-80)°C to (Tmax-75)°C. If the temperature of the second mold is above (Tmax-90)°C, the warpage of the molded product tends to decrease. On the other hand, if the temperature of the second mold is below (Tmax-65)°C, the warpage of the molded product tends to decrease, and since the flatness of the second main surface of the molded product deteriorates due to the influence of thermal shrinkage of the resin or adhesion to the mold, etc., a plate-shaped molded product with good appearance can be obtained.

[0059] In addition, in the present embodiment, it is preferred that the first mold is cooled after being heated. The minimum temperature Tmin of the first mold during cooling is preferably controlled to be in the temperature range of (Tg-75)°C to (Tg-45)°C, more preferably (Tg-70)°C to (Tg-50)°C, and further preferably (Tg-65)°C to (Tg-55)°C. If Tmin is above (Tg-75)°C, the molding cycle can be prevented from becoming extremely long, and thermal degradation of the resin in the barrel can be suppressed. On the other hand, if it is below (Tg-45)°C, there is a tendency for the warpage of the molded product to decrease.

[0060] In the present embodiment, the method for heating the mold is not particularly limited, and any method can be used. For example, a method of arranging a water or oil flow path in the mold and adjusting the mold temperature to a temperature above the Tg of the methacrylic resin composition using a medium such as water or oil; a method of burying a heater in the mold and heating the mold; a method of providing an electrically conductive layer capable of being energized on the surface of the mold and heating the mold by energizing the mold to generate heat; a method of heating the mold from the outside or inside by an induction heating device; a method of heating the mold from the outside by radiating far infrared rays using a halogen lamp or a ceramic heater, etc.

[0061] In addition, in the present embodiment, the cooling method of the mold is not particularly limited, and any method may be used. For example, a method of providing a water or oil flow path in the mold and cooling with a medium such as water or oil may be mentioned.

[0062] In the present embodiment, the temperature rise rate of the surface temperature of the first mold during heating is preferably 1 to 10°C / second, more preferably 1.5 to 10°C / second, and further preferably 2 to 10°C / second. The faster the temperature rise rate, the more effective it is in shortening the cycle time. There is no limit on the cycle time. It can be outside the above range as long as there is no problem of resin degradation caused by heat retention in the barrel. In addition, the temperature drop rate of the surface temperature of the first mold during cooling is preferably 0.5 to 10°C / second, more preferably 1 to 10°C / second, and further preferably 2 to 10°C / second. The faster the temperature drop rate, the more effective it is in shortening the cycle time. As described later, maintaining the mold temperature at a high temperature is effective in improving the transferability. However, if the temperature drop rate is outside this range, it tends to cause the cycle time to be lengthened and the warping of the molded product to be deteriorated, so it is not preferred.

[0063] In this embodiment, the temperature control can be appropriately set by slowing down the speed of heating and cooling or maintaining the temperature at a predetermined time, in addition to heating and cooling at a predetermined speed. In order to achieve good transfer of the convex shape, it is preferred to maintain the temperature at a temperature (preferably above the glass transition temperature) at which the resin flows for a long time. In addition, if the holding time is short, birefringence occurs due to the formation of a skin layer. Therefore, from the viewpoint of suppressing this situation, it is preferred to slow down the cooling speed.

[0064] It is preferred to implement a demoulding process on the surface of the mold. As a demoulding process on the surface of the mold, an organic or inorganic demoulding coating can be appropriately used. For example, organic coatings such as fluorine, silicone, and wax can be used, and inorganic coatings such as DLC, Cr, and Ti can be used. Organic demoulding coatings and inorganic demoulding coatings can be used together. The demoulding coating can be made into a film on the mold by a known wet method or a dry method. However, in the case where the depth of the fine convex shape of the mold is deep or the shape is complex, in the film formation using PVD (Physical Vapor Deposition), such as vacuum evaporation, sputtering, ion plating, etc., there is a tendency that the coating cannot be formed into a film to the deep part of the fine convex shape. From the viewpoint of being able to implement a demoulding coating to the deep part of the fine convex shape and improving the demoulding property of the molded product, it is preferred to use a demoulding agent that dissolves or disperses the demoulding component in a solvent and then applies or sprays it to the mold, and forms a demoulding film by drying or curing.

[0065] (Plate-shaped molded product)

[0066] The plate-shaped molded product of the present embodiment is manufactured by the manufacturing method of the plate-shaped molded product of the present embodiment, characterized in that the plate-shaped molded product comprises a glass transition temperature Tg of 115 to 160° C., a melt viscosity of 270° C., and a viscosity of 1000 sec. -1 The plate-like molded article has no bonding interface and is composed of a single resin composition. One main surface (first main surface) of the plate-like molded article has a plurality of fine convex shapes (hereinafter, also referred to as "fine convex shape portion"), and the other main surface (second main surface) is a plane. In the first main surface, the height a of the convex shapes is 0.5 to 700 μm, the ratio b / a of the pitch b of the convex shapes to the height a of the convex shapes is 0.1 to 2.0, and the projection area of ​​the first main surface is 225 cm 2 above.

[0067] Hereinafter, the shape and the like of the plate-shaped molded product according to the present embodiment will be described in detail.

[0068] The plate-shaped molded product of this embodiment has no bonding interface and is composed of a single resin composition. By injection molding, the fine convex-shaped portion and the plate-shaped portion (the portion other than the fine convex-shaped portion) are molded with a single resin composition to manufacture a molded product having no bonding interface between the fine convex-shaped portion and the plate-shaped portion, thereby obtaining a plate-shaped molded product with less deterioration in appearance due to peeling of the bonding interface.

[0069] In the present embodiment, the fine convex shape formed on the first main surface is not particularly limited, and examples thereof include polygonal cones such as triangular cones, quadrangular cones, and pentagonal cones, curved cones such as circular cones, elliptical cones, semi-circular cones, semi-elliptical cones, and waist-shaped cones (cones with a cross section shaped by connecting the two ends of a pair of parallel straight lines with a semicircle), polygonal cones such as triangular cones, quadrangular cones, and pentagonal cones, circular cones, elliptical cones, semi-circular cones, semi-elliptical cones, and waist-shaped cones (cones with a cross section shaped by connecting the two ends of a pair of parallel straight lines with a semicircle), and polygonal cones such as triangular cones, quadrangular cones, and pentagonal cones. The convex shape may be a truncated cone with a cross section formed by connecting the two ends of a pair of parallel straight lines (a truncated cone with a cross section formed by connecting the two ends of a pair of parallel straight lines), a triangular prism, a quadrangular prism (a cube, a cuboid, etc.), a pentagonal prism, a polygonal prism, a circular cylinder, an elliptical prism, a semi-circular prism, a semi-elliptical prism, a kidney cone (a cylinder with a cross section formed by connecting the two ends of a pair of parallel straight lines with a semicircle), a dome (a structure with a hemisphere, a quarter sphere, an aspherical surface, etc., whose cross-sectional area gradually decreases as it moves upward in the axial direction). In the case of a polygonal cone, a polygonal prism, etc., the corners may be rounded. In addition, the side surface of the convex shape may be a plane or a curved surface.

[0070] These convex shapes may be one type only or a combination of plural types, but are preferably one type only.

[0071] Figure 2 1 is a partial cross-sectional view showing an example of a plate-shaped molded product of the present embodiment in which the fine convex shape is a triangular pyramid. Figure 4 This is a partial cross-sectional view showing an example of a plate-like molded product according to the present embodiment in which the fine convex shape is a quadrangular pyramid trapezoid.

[0072] The convex shape may also be arranged in a straight line, a curve, a dot, etc. In addition, the convex shape may be arranged on the entire surface of the first main surface, or may be arranged only on a part of the first main surface. Figure 1 (A) Figure 3 (A) is a top view (plan view) when an example of a plate-like molded product in which a convex shape is arranged only in a partial area of ​​the first main surface is viewed from the first main surface side.

[0073] In this embodiment, the ratio b / a of the pitch b of the fine convex shape to the height a is 0.1 to 2.0, preferably 0.2 to 2.0, and more preferably 0.3 to 2.0. If b / a is within the above range, the molded product tends to be able to be cleanly demolded while maintaining an excellent mold transfer rate.

[0074] b / a is the average value of the values ​​obtained by measuring the height and pitch of 5 or more convex shapes. Therefore, as long as b / a is within the above range, the height and pitch of each convex shape can be changed arbitrarily.

[0075] The height a of the convex shape is 0.5 to 700 μm, preferably 50 to 650 μm, more preferably 200 to 600 μm, and further preferably 300 to 550 μm. If the height a of the convex shape is within the above range, the present invention tends to effectively reduce warpage of the molded article.

[0076] The pitch b of the convex shapes is preferably in the range of 100 to 500 μm, more preferably 150 to 450 μm, and even more preferably 180 to 400 μm. When the pitch b of the convex shapes is in the above range, warpage of the molded product tends to be effectively reduced.

[0077] It should be noted that in this specification, the height of the convex shape refers to the highest value of the height in the thickness direction of the molded product measured based on the plane portion of the first main surface parallel to the second main surface, and the height a is the average value of the heights of five or more convex shapes. Figure 2 As shown, when the convex shape is a cone, it refers to the height up to the apex of the cone. The height of the convex shape when there is no planar portion parallel to the second main surface on the first main surface can be the highest value among the heights of the convex shape in the thickness direction relative to the average thickness of the molded product.

[0078] In this specification, the pitch of convex shapes refers to the distance between the centers of two adjacent convex shapes when the convex shapes are viewed from above (see Figure 2 , Figure 4 ), the spacing b is the average of the spacings measured for more than 5 convex shapes.

[0079] The height a and the pitch b of the convex shape can be visually measured from an observation image obtained using an optical microscope, an electron microscope, a digital microscope, or the like, and specifically, can be measured by the method described in the Examples described later.

[0080] The size of the convex shape in plan view when viewed from above with the first main surface as the upper surface is preferably 0.1 to 600 μm in diameter, more preferably 0.5 to 500 μm, and even more preferably 1 to 400 μm.

[0081] It should be noted that, when the above-mentioned top-view shape of the convex shape is a line figure, it is set to the length of the width in the direction orthogonal to the line direction, and in other cases, when the above-mentioned top-view shape is a shape other than a circle, it refers to the diameter of its circumscribed circle. The diameter of the top-view shape of the convex shape can be visually measured based on an observation image obtained using an optical microscope, an electron microscope, a digital microscope, etc.

[0082] The dimensions of the convex shapes (height and diameter in plan view) may be the same or different in all the convex shapes.

[0083] The overall shape of the molded article of the present embodiment is not particularly limited as long as it is a plate-like or substantially plate-like shape having a plurality of fine convex shapes on one main surface and a flat surface on the other main surface.

[0084] As the shape when viewed from above with the first main surface having a fine convex shape as the upper surface (top view shape), for example, there can be cited polygons such as triangles, squares, rectangles, parallelograms, trapezoids, pentagons, circles, ellipses, semicircles, semi-ellipses, kidney shapes (shapes formed by connecting the ends of a pair of parallel straight lines with semicircles), donuts, etc. In the case of polygons, the corners may be rounded.

[0085] In addition, when the area of ​​the part with a fine convex shape of the first main surface is set to 100%, the area of ​​the flat part of the second main surface on the back side can be 80% or more. Considering that the molded product is mounted on various products, a part of the second main surface may have a concave-convex part for connecting with the product. The shape of the concave-convex part for connection is not particularly limited. For example, a concave-convex part for connection with a size of 2 to 10 mm and a height of 2 to 10 mm can be provided near the outer periphery of the molded product for fixing to the product.

[0086] Furthermore, from the viewpoint of demolding during molding, a frame for protruding with an ejector pin may be provided on the outer periphery of the molded product.

[0087] In this embodiment, the projected area of ​​the first main surface of the molded product is 225 cm 2 Above, can be 225~2500cm 2 , can also be 225~1000cm 2 When the projected area of ​​the first main surface is within the above range, a molded product having a good appearance can be obtained without causing poor demolding in the molded product.

[0088] It should be noted that, in this specification, the projected area of ​​the first main surface refers to the area of ​​the shape (top view shape) when the molded product is placed in a manner such that the first main surface becomes the upper surface and the first main surface is observed from above. Figure 1 (A) The molded product is 552cm 2 (=230mm×240mm), Figure 3 (A) The molded product is 702cm 2 (=260mm×270mm).

[0089] In this embodiment, the thickness of the molded product is preferably 1.5 mm or more and less than 6 mm, more preferably 2 mm or more and less than 5 mm, and further preferably 2 mm or more and less than 4 mm. The thinner the thickness, the more difficult it is to control the warpage. In addition, the thicker the thickness, the more favorable it is to control the warpage. The cooling during molding takes time, resulting in a temperature difference between the surface and the inside, and the central part is concave, which damages the flatness of the plane and may have an adverse effect on the optical properties of the molded product.

[0090] The size of each main surface of the molded article is not particularly limited and can be set according to the purpose.

[0091] The filling degree of the plate-like molded product of the present embodiment is preferably 0.92 or more, more preferably 0.95 or more, and further preferably 0.99 or more. If the filling degree is 0.92 or more, it can be said that the molded product has a good convex shape.

[0092] The filling degree is a value calculated by the following formula based on the height a of the convex shape and the depth of the concave shape in the first mold for forming the convex shape, and is an average value of four points. Specifically, it can be measured by the method described in the examples described below.

[0093] (Filling degree) = (height a of the convex shape of the molded product) / (depth of the concave shape of the mold)

[0094] When the plate-shaped molded product of this embodiment is Figure 1 When the second main surface has no uneven portion as shown, the warpage is preferably 0.4 mm or less, more preferably 0.35 mm or less, and further preferably 0.3 mm or less. If the warpage is 0.4 mm or less, it can be said that the molded product has good dimensional accuracy.

[0095] In addition, the square root of the area value when the region where the convex shape is formed is viewed from above with the surface where the convex shape is formed as the upper surface is calculated (for example, Figure 1 In the figure, the shaping surface area is 210 mm square, so the square root is 210 mm). If the warpage relative to the obtained value is 0.50% or less, it can be judged that the dimensional accuracy of the molded product is in the preferred range. It is more preferably 0.44% or less, and further preferably 0.38% or less.

[0096] It should be noted that the warpage refers to the amount of warpage when the outer periphery of the molded product is evenly divided into four points on the metal platform with the first main surface as the upper surface. Figure 1 When measuring the gap formed between the molded product and the platform in 15a to 15d), it is the value of the location where the gap is the largest. Specifically, it can be measured by the method described in the examples described later.

[0097] For the plate-shaped molded product of this embodiment, the birefringence value as the in-plane retardation is preferably 100 nm or less, more preferably 50 nm or less, and further preferably 20 nm or less. If the in-plane retardation is within the above range, it is unlikely to have an adverse effect on optical properties.

[0098] In addition, the in-plane retardation can be measured by the method described in Examples described later.

[0099] For the plate-shaped molded product of the present embodiment, the amount of methyl methacrylate (MMA) contained in the plate-shaped molded product is preferably 1600 to 6000 mass ppm, more preferably 1800 to 5000 mass ppm, and further preferably 2000 to 4000 mass ppm. If the amount of MMA in the plate-shaped molded product is 6000 mass ppm or less, there is a tendency that a molded product with low yellowness and good appearance can be obtained. On the other hand, if the amount of MMA in the plate-shaped molded product is 1600 mass ppm or more, there is a tendency that a molded product with low yellowness can be obtained with good filling of fine convex shapes.

[0100] In addition, the amount of MMA contained in the plate-shaped molded product can be measured by the method described in the Examples mentioned later.

[0101] The yellowness index (YI) of the plate-like molded product of the present embodiment is preferably 3.0 to 10.0, more preferably 3.0 to 9.0, and even more preferably 3.0 to 8.0. When the yellowness index (YI) is within the above range, the yellowness tends to be low and the appearance tends to be good.

[0102] In addition, the yellowness index (YI) can be measured by the method described in the Examples mentioned later.

[0103] (Methacrylic resin composition)

[0104] The methacrylic resin composition used in the method for producing a plate-shaped molded product according to the present embodiment is characterized in that it contains a methacrylic resin and may optionally contain additives in addition thereto, and may also contain other thermoplastic resins, rubber polymers, and the like other than the methacrylic resin.

[0105] -Methacrylic resin-

[0106] The properties of the methacrylic resin used in the present embodiment are described below.

[0107] The methacrylic resin used in the present embodiment is not particularly limited, and for example, a resin having a structural unit derived from methyl methacrylate as a main body can be cited, wherein the resin can be cited as a homopolymer of methyl methacrylate, or a copolymer of methyl methacrylate and any one or more of copolymerizable monomers such as methyl methacrylate, methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, butyl acrylate, acrylonitrile, acrylic acid, methacrylic acid, vinyl pyridine, vinyl morpholine, vinyl pyridone tetrahydrofurfuryl acrylate, N,N-dimethylaminoethyl acrylate, N,N-dimethylacrylamide, 2-hydroxyacrylate, ethyl 2-(hydroxymethyl)acrylate, ethylene glycol monoacrylate, glycerol monoacrylate, maleic anhydride, N-cyclohexylmaleimide, N-phenylmaleimide, styrene or α-methylstyrene. In addition, heat-resistant methacrylic resins having a structural unit derived from methyl methacrylate and a lactone ring or glutarimide in the main chain, methyl methacrylate, and low hygroscopic methacrylic resins are included. These may be used alone or in combination of two or more.

[0108] In addition, "comprising mainly structural units derived from methyl methacrylate" means that the structural units derived from methyl methacrylate account for 50% by mass or more of the structural units in the methacrylic resin.

[0109] From the viewpoint of transparency and heat resistance, the methacrylic resin in the present embodiment is preferably a methacrylic resin having a structural unit having a ring structure.

[0110] As the structural unit having the ring structure, it is preferred that the structural unit comprises at least one structural unit selected from the group consisting of a structural unit derived from an N-substituted maleimide monomer, a glutarimide-based structural unit, an aromatic vinyl structural unit, an alicyclic vinyl structural unit, and a lactone ring structural unit. In addition, from the viewpoint of being easy to highly control optical properties such as intrinsic birefringence and photoelastic coefficient without mixing with other thermoplastic resins, it is particularly preferred that the structural unit having a ring structure comprises a structural unit derived from an N-substituted maleimide monomer.

[0111] --Structural Units from N-Substituted Maleimide Monomers--

[0112] Next, the structural unit derived from the N-substituted maleimide monomer will be described.

[0113] The structural unit derived from the N-substituted maleimide monomer may be at least one structural unit selected from the group consisting of a structural unit represented by the following formula (1) and a structural unit represented by the following formula (2), and preferably, it is formed of both structural units represented by the following formula (1) and the following formula (2).

[0114]

[0115] In formula (1), R 1 represents any one of an arylalkyl group having 7 to 14 carbon atoms and an aryl group having 6 to 14 carbon atoms, and R 2 and R 3 Each independently represents a hydrogen atom, an oxygen atom, a sulfur atom, an alkyl group having 1 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms.

[0116] In addition, in R 2 or R 3 In the case of an aryl group, R 2 or R 3 A halogen atom may be contained as a substituent.

[0117] In addition, R 1 It may be substituted with a substituent such as a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a nitro group, or a benzyl group.

[0118]

[0119] In formula (2), R 4 represents any one of a hydrogen atom, a cycloalkyl group having 3 to 12 carbon atoms, and an alkyl group having 1 to 12 carbon atoms, and R 5 and R 6Each independently represents a hydrogen atom, an oxygen atom, a sulfur atom, an alkyl group having 1 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms.

[0120] In the above formula (1), the arylalkyl group having 7 to 14 carbon atoms is not limited, and examples thereof include benzyl, phenylethyl, phenylpropyl, naphthylmethyl, naphthylethyl, and naphthylpropyl.

[0121] In the above formula (1) and formula (2), the aryl group having 6 to 14 carbon atoms is not limited, and examples thereof include phenyl, tolyl, xylyl, naphthyl, biphenylyl, anthracenyl, and phenanthryl.

[0122] In the above formula (1) and formula (2), the alkyl group having 1 to 12 carbon atoms may be straight-chain or branched, and is not particularly limited. Examples thereof include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, 2-methylbutyl, n-pentyl, 2-pentyl, 3-pentyl, 2,2-dimethylpropyl, n-hexyl, heptyl, n-octyl, 1,1,3,3-tetramethylbutyl, 2-ethylhexyl, nonyl, decyl, undecyl, and dodecyl.

[0123] In the above formula (1), examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.

[0124] In the above formula (1), the alkoxy group having 1 to 6 carbon atoms is not limited, and examples thereof include methoxy, ethoxy, n-butoxy, and methoxyethoxy.

[0125] In the above formula (1), the cycloalkyl group having 3 to 12 carbon atoms is not limited, and examples thereof include cyclopropyl, cyclopropylmethyl, cyclobutyl, cyclopentyl, cyclohexyl, cyclohexylmethyl, trimethylcyclohexyl, thujyl, norbornyl, bornyl, norcaryl, caryl, menthyl, norpinyl, pinyl, 1-adamantyl, and 2-adamantyl.

[0126] A specific example is shown below.

[0127] Examples of the monomer (N-aryl maleimide, N-aromatic substituted maleimide, etc.) forming the structural unit represented by formula (1) include N-phenylmaleimide, N-benzylmaleimide, N-(2-chlorophenyl)maleimide, N-(4-chlorophenyl)maleimide, N-(4-bromophenyl)maleimide, N-(2-methylphenyl)maleimide, N-(2,6-xylyl)maleimide, N-(2-ethylphenyl)maleimide, N-(2-methoxyphenyl)maleimide, N-(2-hydroxy ... -(2-nitrophenyl)maleimide, N-(2,4,6-trimethylphenyl)maleimide, N-(4-benzylphenyl)maleimide, N-(2,4,6-tribromophenyl)maleimide, N-naphthylmaleimide, N-anthrylmaleimide, 3-methyl-1-phenyl-1H-pyrrole-2,5-dione, 3,4-dimethyl-1-phenyl-1H-pyrrole-2,5-dione, 1,3-diphenyl-1H-pyrrole-2,5-dione, 1,3,4-triphenyl-1H-pyrrole-2,5-dione, etc.

[0128] Among these monomers, N-phenylmaleimide and N-benzylmaleimide are preferred from the viewpoint of excellent optical properties such as heat resistance and birefringence.

[0129] These monomers may be used alone or in combination of two or more.

[0130] Examples of the monomer forming the structural unit represented by formula (2) include N-methylmaleimide, N-ethylmaleimide, N-n-propylmaleimide, N-isopropylmaleimide, N-n-butylmaleimide, N-isobutylmaleimide, N-sec-butylmaleimide, N-tert-butylmaleimide, N-n-pentylmaleimide, N-n-hexylmaleimide, N-n-heptylmaleimide, N -n-octylmaleimide, N-laurylmaleimide, N-cyclopentylmaleimide, N-cyclohexylmaleimide, 1-cyclohexyl-3-methyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3,4-dimethyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3-phenyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3,4-diphenyl-1H-pyrrole-2,5-dione, etc.

[0131] Among these monomers, N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide, and N-cyclohexylmaleimide are preferred from the viewpoint of excellent weather resistance of methacrylic resins, and N-cyclohexylmaleimide is particularly preferred from the viewpoint of excellent low hygroscopicity required for optical materials in recent years.

[0132] These monomers may be used alone or in combination of two or more.

[0133] In the methacrylic resin in the methacrylic resin composition, it is particularly preferred to use the structural unit represented by the formula (1) and the structural unit represented by the formula (2) in combination, because highly controlled birefringence characteristics can be expressed.

[0134] The molar ratio (X1 / X2) of the content (X1) of the structural unit represented by the formula (1) to the content (X2) of the structural unit represented by the formula (2) is preferably greater than 0 and less than 15, and more preferably greater than 0 and less than 10. When the molar ratio (X1 / X2) is within this range, the plate-like molded product of the present embodiment maintains transparency without yellowing, and exhibits good heat resistance and good photoelastic properties without impairing environmental resistance.

[0135] As the content of the structural unit derived from the N-substituted maleimide monomer, the methacrylic resin is set to 100% by mass, preferably in the range of 5 to 40% by mass, and more preferably in the range of 5 to 35% by mass. When the content of the structural unit derived from the N-substituted maleimide monomer is within this range, the methacrylic resin can obtain a more sufficient improvement in heat resistance, and further, a more preferred improvement in weather resistance, low water absorption, and optical properties can be obtained. It should be noted that setting the content of the structural unit derived from the N-substituted maleimide monomer to 40% by mass or less can effectively prevent the decrease in the physical properties of the methacrylic resin caused by the decrease in the reactivity of the monomer components during the polymerization reaction and the increase in the amount of unreacted and residual monomers.

[0136] In addition, by appropriately adjusting the content of the structural unit derived from the N-substituted maleimide monomer within this range, the birefringence caused by the orientation or residual stress during molding can be reduced, and a plate-shaped molded product having an average value of the absolute value of the in-plane phase difference of less than 100 nm can be obtained. Depending on the type of N-substituted maleimide, the most suitable content of the structural unit derived from the N-substituted maleimide monomer is different. For example, when methyl methacrylate is used as the methacrylate monomer and N-phenylmaleimide and N-cyclohexylmaleimide are used as the N-substituted maleimide monomer, it is preferably adjusted within the range of 79 to 83% by mass of the structural unit derived from methyl methacrylate, 6 to 8% by mass of the structural unit derived from N-phenylmaleimide, and 11 to 13% by mass of the structural unit derived from N-cyclohexylmaleimide.

[0137] The methacrylic resin having a structural unit derived from an N-substituted maleimide monomer may contain a structural unit derived from other monomers copolymerizable with the methacrylate monomer and the N-substituted maleimide monomer within a range not impairing the purpose of the present invention.

[0138] For example, examples of the other copolymerizable monomers include aromatic vinyl groups; unsaturated nitriles; acrylic acid esters having a cyclohexyl group, a benzyl group, or an alkyl group having 1 to 18 carbon atoms; glycidyl compounds; and unsaturated carboxylic acids.

[0139] Examples of the aromatic vinyl group include styrene, α-methylstyrene, and divinylbenzene.

[0140] Examples of the unsaturated nitrile include acrylonitrile, methacrylonitrile, and ethacrylonitrile.

[0141] Examples of the acrylic acid ester include methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, and butyl acrylate.

[0142] Examples of the glycidyl compound include glycidyl (meth)acrylate and the like.

[0143] Examples of the unsaturated carboxylic acids include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and half esters or anhydrides thereof.

[0144] The structural unit derived from the above-mentioned other copolymerizable monomer may be present in only one kind or in two or more kinds.

[0145] The content of the structural unit derived from other copolymerizable monomers is preferably 0 to 10% by mass, more preferably 0 to 9% by mass, and even more preferably 0 to 8% by mass, based on 100% by mass of the methacrylic resin.

[0146] When the content of the structural unit derived from other monomers is within this range, the molding processability and mechanical properties of the resin can be improved without impairing the original effect of the introduction of the ring structure, which is preferred.

[0147] It should be noted that the content of the structural unit derived from the N-substituted maleimide monomer and the content of the structural unit derived from other copolymerizable monomers can be expressed by 1 H-NMR determination and 13 It can be determined by C-NMR measurement. 1 H-NMR determination and 13 C-NMR measurement can be performed at a measurement temperature of 40° C. using, for example, CDCl 3 or DMSO-d 6 as a measurement solvent.

[0148] --Glutarimide structural unit--

[0149] Examples of the methacrylic resin having a glutarimide structural unit include methacrylic resins having a glutarimide structural unit described in JP-A-2006-249202, JP-A-2007-009182, JP-A-2007-009191, JP-A-2011-186482, and JP-A-2012 / 114718, and can be formed by the methods described in the publications.

[0150] The glutarimide structural unit constituting the methacrylic resin can be formed after the resin is polymerized.

[0151] Specifically, the glutarimide structural unit can be represented by the following general formula (3).

[0152]

[0153] In the above general formula (3), preferably, R 7 and R 8 are independently a hydrogen atom or a methyl group, R 9 is any one of a hydrogen atom, a methyl group, a butyl group, and a cyclohexyl group, and more preferably, R 7 is methyl, R 8 is a hydrogen atom, R 9 It is methyl.

[0154] The glutarimide-based structural units may contain a single type or a plurality of types.

[0155] In the methacrylic resin having a glutarimide structural unit, the content of the glutarimide structural unit is preferably in the range of 3 to 70 mass %, more preferably in the range of 3 to 60 mass %, based on 100 mass % of the methacrylic resin.

[0156] When the content of the glutarimide structural unit is within the above range, a resin having excellent molding processability, heat resistance, and optical properties can be obtained, which is preferred.

[0157] In addition, by appropriately adjusting the content of the glutarimide structural unit within this range, the birefringence caused by the orientation or residual stress during molding can be reduced, and a plate-shaped molded product having an average value of the absolute value of the in-plane phase difference of 100 nm or less can be obtained. 7 ~R 9 The content of the most suitable glutarimide structural unit varies with the type of substituent. For example, when R 7 and R 8 is a hydrogen atom and R 9In the case of a methyl group, when the content of the glutarimide structural unit is in the range of 3 to 10 mass %, birefringence caused by orientation or residual stress during molding can be reduced, and a plate-shaped molded product having an average absolute value of in-plane retardation of 100 nm or less can be obtained.

[0158] In addition, the content of the glutarimide structural unit in the methacrylic resin can be determined using the method described in the above-mentioned patent document.

[0159] The methacrylic resin having a glutarimide structural unit may further contain an aromatic vinyl monomer unit as necessary.

[0160] The aromatic vinyl monomer is not particularly limited, and examples thereof include styrene and α-methylstyrene, with styrene being preferred.

[0161] The content of the aromatic vinyl unit in the methacrylic resin having a glutarimide structural unit is not particularly limited, but is preferably 0 to 20% by mass based on 100% by mass of the methacrylic resin having a glutarimide structural unit.

[0162] When the content of the aromatic vinyl unit is within the above range, heat resistance and excellent photoelastic properties can be achieved at the same time, which is preferred.

[0163] For example, when a methyl methacrylate-styrene copolymer obtained by copolymerizing methyl methacrylate as a methacrylate monomer and styrene as an aromatic vinyl monomer is subjected to glutarimidization to obtain a resin, by adjusting the content of structural units derived from methyl methacrylate to 65 to 90% by mass, structural units derived from styrene to 5 to 15% by mass, and glutarimide-based structural units to 5 to 20% by mass, it is possible to reduce birefringence caused by orientation or residual stress during molding, and to obtain a plate-shaped molded product having an average value of the absolute value of the in-plane retardation of 100 nm or less.

[0164] --Aromatic vinyl structural unit--

[0165] The aromatic vinyl structural unit is not particularly limited, and examples thereof include structural units derived from styrene and α-methylstyrene, and a structural unit derived from styrene is preferred.

[0166] --Alicyclic vinyl structural unit--

[0167] The alicyclic vinyl structural unit can be formed by the methods described in, for example, JP-A-2006-291184, JP-A-2006-291184, JP-A-2014-77043, JP-A-2014-77044, and the like.

[0168] --Lactone ring structural unit--

[0169] The methacrylic resin having a lactone ring structural unit can be formed by the methods described in, for example, JP-A-2001-151814, JP-A-2004-168882, JP-A-2005-146084, JP-A-2006-96960, JP-A-2006-171464, JP-A-2007-63541, JP-A-2007-297620, JP-A-2010-180305, and the like.

[0170] The lactone ring structural unit constituting the methacrylic resin may be formed after the resin is polymerized.

[0171] As the lactone ring structural unit in the present embodiment, a six-membered ring is preferred because of its excellent stability in the ring structure.

[0172] As the six-membered lactone ring structural unit, for example, a structure represented by the following general formula (4) is particularly preferred.

[0173]

[0174] In the above general formula (4), R 10 , R 11 and R 12 They are independently a hydrogen atom or an organic residue having 1 to 20 carbon atoms.

[0175] As the organic residue, for example, there can be mentioned saturated aliphatic hydrocarbon groups (alkyl groups, etc.) having 1 to 20 carbon atoms, such as methyl, ethyl, propyl, etc.; unsaturated aliphatic hydrocarbon groups (alkenyl groups, etc.) having 2 to 20 carbon atoms, such as vinyl, propenyl, etc.; aromatic hydrocarbon groups (aryl groups, etc.) having 6 to 20 carbon atoms, such as phenyl, naphthyl, etc.; groups in which one or more hydrogen atoms in these saturated aliphatic hydrocarbon groups, unsaturated aliphatic hydrocarbon groups, and aromatic hydrocarbon groups are substituted with at least one group selected from the group consisting of hydroxyl groups, carboxyl groups, ether groups, and ester groups; and the like.

[0176] The lactone ring structural unit can be formed, for example, by copolymerizing an acrylic monomer having a hydroxyl group and a methacrylate monomer such as methyl methacrylate, introducing a hydroxyl group and an ester group or a carboxyl group into the molecular chain, and then subjecting the hydroxyl group to dealcoholization (esterification) or dehydration condensation (hereinafter also referred to as "cyclization condensation reaction") with the ester group or the carboxyl group.

[0177] Examples of acrylic monomers having a hydroxyl group used in the polymerization include 2-(hydroxymethyl)acrylic acid, 2-(hydroxyethyl)acrylic acid, 2-(hydroxymethyl)acrylic acid alkyl esters (e.g., methyl 2-(hydroxymethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, isopropyl 2-(hydroxymethyl)acrylate, n-butyl 2-(hydroxymethyl)acrylate, tert-butyl 2-(hydroxymethyl)acrylate), and 2-(hydroxyethyl)acrylic acid alkyl esters. Preferred are 2-(hydroxymethyl)acrylic acid and 2-(hydroxymethyl)acrylic acid alkyl esters, which are monomers having a hydroxyalkyl moiety, and particularly preferred are methyl 2-(hydroxymethyl)acrylate and ethyl 2-(hydroxymethyl)acrylate.

[0178] The content of the lactone ring structural unit in the methacrylic resin having a lactone ring structural unit is preferably 5 to 40% by mass, more preferably 5 to 35% by mass, based on 100% by mass of the methacrylic resin.

[0179] If the content of the lactone ring structural unit is within this range, the effects of introducing the ring structure, such as improving solvent resistance or improving surface hardness, can be exhibited while maintaining molding processability. In addition, by appropriately adjusting the content of the lactone ring structural unit within this range, the birefringence caused by orientation or residual stress during molding can be reduced, and a plate-shaped molded product having an average value of the absolute value of the in-plane phase difference of 100 nm or less can be obtained.

[0180] In addition, the content of the lactone ring structure in the methacrylic resin can be determined using the method described in the above-mentioned patent document.

[0181] The methacrylic resin having a lactone ring structural unit may have a structural unit derived from other monomers copolymerizable with the methacrylate monomer and the acrylic monomer having a hydroxyl group.

[0182] Examples of such other copolymerizable monomers include monomers having polymerizable double bonds such as styrene, vinyltoluene, α-methylstyrene, α-hydroxymethylstyrene, α-hydroxyethylstyrene, acrylonitrile, methacrylonitrile, methylallyl alcohol, ethylene, propylene, 4-methyl-1-pentene, vinyl acetate, 2-hydroxymethyl-1-butene, methyl vinyl ketone, N-vinyl pyrrolidone, and N-vinyl carbazole.

[0183] These other monomers (constituent units) may be present in one type or in two or more types.

[0184] The content of the structural unit derived from other copolymerizable monomers is preferably 0 to 20% by mass based on 100% by mass of the methacrylic resin, more preferably less than 10% by mass, and further preferably less than 7% by mass from the viewpoint of weather resistance.

[0185] The methacrylic resin in the present embodiment may have only one type of the structural unit derived from the other copolymerizable monomer, or may have two or more types.

[0186] -Method for producing methacrylic resin-

[0187] The method for producing the methacrylic resin according to the present embodiment is described below.

[0188] In the manufacturing method in the present embodiment, as the polymerization form, intermittent (batch), semi-intermittent (semi-batch), and continuous can be used. Here, intermittent refers to a process in which the total amount of raw materials is put into the reactor to start and continue the reaction, and the product is recovered after the reaction is completed. In addition, semi-intermittent refers to a process in which either raw material input or product recovery is performed simultaneously during the reaction. Further, continuous refers to a process in which raw material input and product recovery are performed simultaneously during the reaction. As a manufacturing method for methacrylic resin in the present embodiment, from the viewpoint of precisely controlling the composition of the copolymer, a semi-intermittent form in which a part of the raw materials are input after the reaction starts is preferably used.

[0189] The continuous type is not preferred as the manufacturing method in the present embodiment for the following reasons. For the continuous type, when a complete mixing reactor is used to carry out the polymerization reaction, there is an advantage that the difference in monomer composition between the components with different molecular weights in the methacrylic resin can be reduced, and more unreacted monomers remain after polymerization, so there is a tendency to have an adverse effect on the color tone. On the other hand, when a plug flow reactor is used, the amount of unreacted monomers can be reduced, and there is a tendency that the difference in monomer composition between the components with different molecular weights in the methacrylic resin becomes larger. When a plurality of complete mixing reactors or a complete mixing reactor and a plug flow reactor are combined in series, the amount of unreacted monomers can also be reduced, but there is a tendency that the difference in monomer composition between the above-mentioned components becomes larger.

[0190] The polymerization solvent is not particularly limited, and examples thereof include aromatic hydrocarbons such as toluene, xylene, ethylbenzene, and cumene; esters such as methyl isobutyrate; ketones such as methyl isobutyl ketone, butyl cellosolve, methyl ethyl ketone, and cyclohexanone; and polar solvents such as dimethylformamide and 2-methylpyrrolidone.

[0191] Furthermore, an alcohol such as methanol, ethanol, or isopropanol may be used in combination as a polymerization solvent within a range that does not inhibit the dissolution of the polymerization product during polymerization.

[0192] The amount of solvent during polymerization is not particularly limited as long as it is an amount that allows polymerization, does not cause precipitation of copolymers or used monomers during production, and can be easily removed. For example, when the total amount of the formulated monomers is set to 100 parts by mass, it is preferably set to 10 to 200 parts by mass, more preferably 25 to 200 parts by mass, further preferably 50 to 200 parts by mass, and further preferably 50 to 150 parts by mass.

[0193] As the polymerization initiator, any initiator commonly used in free radical polymerization can be used, for example, organic peroxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, di-tert-butyl peroxide, lauroyl peroxide, benzoyl peroxide, tert-butyl peroxyisopropyl carbonate, tert-amyl peroxy-2-ethylhexanoate, tert-amyl peroxyisononanoate, and 1,1-di(tert-butylperoxy)cyclohexane; and azo compounds such as 2,2'-azobis(isobutyronitrile), 1,1'-azobis(cyclohexanecarbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), and dimethyl-2,2'-azobisisobutyrate.

[0194] These may be used alone or in combination of two or more.

[0195] These polymerization initiators may be added at any stage as long as the polymerization reaction is in progress.

[0196] The amount of the polymerization initiator added may be 0.01 to 1 part by mass, preferably 0.05 to 0.5 parts by mass, based on 100 parts by mass of the total amount of the monomers used in the polymerization.

[0197] As the chain transfer agent, a chain transfer agent commonly used in free radical polymerization can be used, for example, thiol compounds such as n-butyl mercaptan, n-octyl mercaptan, n-decyl mercaptan, n-dodecyl mercaptan, 2-ethylhexyl thioglycolate; halogen compounds such as carbon tetrachloride, dichloromethane, bromoform; unsaturated hydrocarbon compounds such as α-methylstyrene dimer, α-terpinene, dipentene, terpinolene, etc., etc. can be mentioned.

[0198] These may be used alone or in combination of two or more.

[0199] These chain transfer agents may be added at any stage without particular limitation as long as the polymerization reaction is in progress.

[0200] The amount of the chain transfer agent added may be 0.01 to 1 part by mass, preferably 0.05 to 0.5 parts by mass, based on 100 parts by mass of the total amount of the monomers used in the polymerization.

[0201] There are no particular limitations on the method for recovering a polymer from a polymerization solution obtained by solution polymerization. For example, there may be a method in which, after adding the polymerization solution in the presence of an excess of a poor solvent such as a hydrocarbon solvent or an alcohol solvent in which the polymerization product obtained by the polymerization is not dissolved, the solution is treated with a homogenizer (emulsification dispersion), and the unreacted monomers are subjected to a pretreatment such as liquid-liquid extraction or solid-liquid extraction to separate them from the polymerization solution; or a method in which the polymerization solvent and unreacted monomers are separated through a process called a devolatilization process to recover the polymerization product.

[0202] Here, the devolatilization step refers to a step of removing volatile components such as the polymerization solvent, residual monomers, and reaction by-products under heating and reduced pressure conditions.

[0203] As the apparatus used in the devolatilization process, for example, there can be cited a devolatilization device composed of a tubular heat exchanger and a devolatilization tank; a thin film evaporator such as Wiprene and Exeva manufactured by Kobelco Environmental Solutions, and KONTRO and tilted-wing KONTRO manufactured by Hitachi, Ltd.; an extruder with vents having a residence time and a surface area sufficient to exert devolatilization performance; etc.

[0204] A devolatilization step or the like using a devolatilization device in which two or more of these devices are combined can also be utilized.

[0205] From the viewpoint of improving color tone, it is preferred to use a devolatilization device which mainly includes a heat exchanger and a decompression container and does not have a rotating part as its structure.

[0206] Specifically, a devolatilization device including a devolatilization tank having a heat exchanger disposed on top and a decompression unit attached to a decompression container having a size capable of decompression, and a discharge device such as a gear pump for discharging the devolatilized polymer can be used.

[0207] The devolatilization device is a device that preheats the polymerization solution by feeding it to a heated heat exchanger disposed on the upper part of the reduced pressure container, and then feeding it to a devolatilization tank under heating and reduced pressure to separate and remove the polymerization solvent, unreacted raw material mixture, polymerization by-products, etc. from the copolymer. The heat exchanger may be a multi-tube heat exchanger, a fin heat exchanger, a plate heat exchanger having a plate-type flow path and a heater, etc. By using a devolatilization device without a rotating part as described above, a methacrylic resin having a good color tone can be obtained, which is preferred.

[0208] The treatment temperature in the devolatilizer is preferably 150 to 350° C., more preferably 170 to 300° C., and further preferably 200 to 280° C. By setting the lower limit temperature or higher, residual volatile components can be suppressed, and by setting the upper limit temperature or lower, coloration and decomposition of the obtained acrylic resin can be suppressed.

[0209] -additive-

[0210] The methacrylic resin composition of the present embodiment may contain various additives within a range not significantly impairing the effects of the present invention.

[0211] The additives are not particularly limited, and examples thereof include antioxidants, light stabilizers such as hindered amine light stabilizers, ultraviolet absorbers, release agents, other thermoplastic resins other than methacrylic resins, paraffin-based processing oils, naphthenic processing oils, aromatic processing oils, paraffin, organopolysiloxane, mineral oil and other softeners and plasticizers, flame retardants, antistatic agents, inorganic fillers such as organic fibers and pigments such as iron oxide, reinforcing agents such as glass fibers, carbon fibers and metal whiskers, colorants, organic phosphorus compounds such as phosphites, phosphonites and phosphates, or mixtures thereof.

[0212] --Antioxidants--

[0213] The methacrylic resin composition of the present embodiment preferably contains an antioxidant for suppressing deterioration or coloration during molding or use.

[0214] As the antioxidant, it is not limited to the following substances, for example, hindered phenol antioxidants, phosphorus antioxidants, sulfur antioxidants, etc. can be cited. For the methacrylic resin composition of the present embodiment, it is critical to keep the resin at a high temperature in the mold cavity, and set a moderate cooling time to improve the transferability of the fine convex shape shaping part of the first mold and control the strain or warping height of the molded product surface. When experiencing a long-term thermal history, in order to obtain the desired thermal stability, it is necessary to increase the amount of thermal stabilizer added. From the viewpoint of inhibiting the exudation of the thermal stabilizer or preventing adhesion to the mold, it is preferred to use a plurality of thermal stabilizers in combination, for example, it is preferred to use at least one selected from a phosphorus antioxidant and a sulfur antioxidant and a hindered phenol antioxidant in combination.

[0215] These antioxidants may be used alone or in combination of two or more.

[0216] The hindered phenol antioxidant is not limited to the following substances, and examples thereof include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], diethylene thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,3',3",5,5',5"-hexa-tert-butyl-a,a',a"-(mesitylene-2,4,6-triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, 4,6-bis(dodecylthiomethyl)-o-cresol, ethylenebis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1H,3H,5H)-trione, 1,3,5-tris[(4-tert-butyl-3-hydroxy-2,6-xylyl)methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazine-2-ylamine)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, 2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate, and the like.

[0217] Particularly preferred are pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate.

[0218] In addition, as the hindered phenol antioxidant of the antioxidant, a commercially available phenol antioxidant may be used. Such commercially available phenol antioxidant is not limited to the following substances, and examples thereof include Irganox 1010 (Irganox 1010: pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], manufactured by BASF (BASF)), Irganox 1076 (Irganox 1076: octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, manufactured by BASF (BASF)), Irganox 1330 (Irganox 1330: 3,3',3", 5,5',5"-hexa-tert-butyl-a,a',a"-(mesitylene-2,4,6-triyl)tri-p-cresol, manufactured by BASF (BASF)), and Irganox 3114 (Irganox 3114: 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, manufactured by BASF), Irganox 3125 (Irganox 3125, manufactured by BASF), ADK STAB AO-60 (pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], manufactured by ADEKA), ADK STAB AO-80 (3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane, manufactured by ADEKA), Sumilizer BHT (Sumilizer BHT, manufactured by Sumitomo Chemical Co., Ltd.), Cyanox 1790 (Cyanox 1790, manufactured by Cytec Co., Ltd.), Sumilizer GA-80 (Sumilizer GA-80, manufactured by Sumitomo Chemical Co., Ltd.), Sumilizer GS (Sumilizer GS: 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, manufactured by Sumitomo Chemical Co., Ltd.), Sumilizer GM (Sumilizer GM: 2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate, manufactured by Sumitomo Chemical Co., Ltd.), vitamin E (manufactured by Eisai Co., Ltd.), and the like.

[0219] Among these commercially available phenolic antioxidants, Irganox 1010, ADK STAB AO-60, ADK STAB AO-80, Irganox 1076, Sumilizer GS, and the like are preferred from the viewpoint of the effect of imparting thermal stability to the resin.

[0220] These may be used alone or in combination of two or more.

[0221] In addition, the phosphorus antioxidant as the antioxidant is not limited to the following substances, and examples thereof include tris(2,4-di-tert-butylphenyl)phosphite, bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethylphosphite, tetrakis(2,4-di-tert-butylphenyl)(1,1-biphenyl)-4,4'-diylbisphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, Tetraol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tetrakis(2,4-tert-butylphenyl)(1,1-biphenyl)-4,4'-diylbisphosphonate, di-tert-butyl-m-cresol-phosphonate, 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, and the like.

[0222] Furthermore, a commercially available phosphorus antioxidant may be used as the phosphorus antioxidant. Such commercially available phosphorus antioxidants are not limited to the following substances, and examples thereof include Irgafos 168 (Irgafos 168: tris(2,4-di-tert-butylphenyl)phosphite, manufactured by BASF), Irgafos 12 (Irgafos 12: tris[2-[[2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphin-6-yl]oxy]ethyl]amine, manufactured by BASF), Irgafos 38 (Irgafos 38: bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethylphosphite, manufactured by BASF), ADK STAB 329K (ADK STAB-229K, manufactured by ADEKA), ADK STAB PEP-36 (ADK STAB PEP-36, manufactured by ADEKA), ADK STAB PEP-36A (ADK STAB PEP-36A, manufactured by ADEKA), ADK STAB PEP-8 (ADK STAB PEP-8, manufactured by ADEKA), ADK STAB HP-10 (ADK STAB HP-10, manufactured by ADEKA), ADK STAB 2112 (ADK STAB 2112, manufactured by ADEKA), ADK STAB 1178 (ADK STAB 1178, manufactured by ADEKA), ADK STAB 1500 (ADK STAB 1500, manufactured by ADEKA), Sandstab P-EPQ (manufactured by Clariant), Weston 618 (manufactured by General Electric (GE)), Weston 619G (manufactured by General Electric (GE)), Ultranox 626 (manufactured by General Electric (GE)), Sumilizer GP (Sumilizer GP: 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphinyl)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, manufactured by Sumitomo Chemical Co., Ltd.), HCA (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, manufactured by Sanko Co., Ltd.), and the like.

[0223] Among these commercially available phosphorus-based antioxidants, Irgafos 168, ADK STAB PEP-36, ADK STAB PEP-36A, ADK STAB HP-10, and ADK STAB 1178 are preferred, and ADK STAB PEP-36A and ADK STAB PEP-36 are particularly preferred, from the viewpoint of the effect of imparting thermal stability to the resin and the effect of combined use with multiple antioxidants.

[0224] These phosphorus-based antioxidants may be used alone or in combination of two or more.

[0225] The sulfur-based antioxidant as the antioxidant is not limited to the following substances, and examples thereof include 2,4-bis(dodecylthiomethyl)-6-methylphenol (Irganox 1726, manufactured by BASF), 2,4-bis(octylthiomethyl)-6-methylphenol (Irganox 1520L, manufactured by BASF), 2,2-bis{[3-(dodecylmercapto)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylmercapto]propionate] (ADK STAB AO-412S, manufactured by ADEKA), 2,2-bis{[3-(dodecylmercapto)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylmercapto]propionate] (KEMINOX PLS, manufactured by CHEMIPROKASEI Co., Ltd.). (manufactured by KAISHA, LTD.), ditridecyl 3,3'-thiodipropionate (AO-503, manufactured by ADEKA), and the like.

[0226] Among these commercially available sulfur-based antioxidants, ADK STAB AO-412S and KEMINOX PLS are preferred from the viewpoint of the effect of imparting thermal stability to the resin, the effect of combined use with a plurality of antioxidants, and the viewpoint of handleability.

[0227] These sulfur-based antioxidants may be used alone or in combination of two or more.

[0228] The content of the antioxidant may be an amount that can obtain the effect of improving thermal stability. If the content is excessive, there is a concern that bleeding out may occur during processing. Therefore, the content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, further preferably 1 part by mass or less, further preferably 0.8 part by mass or less, further preferably 0.01 to 0.8 part by mass, and particularly preferably 0.01 to 0.5 part by mass, based on 100 parts by mass of the methacrylic resin.

[0229] --UV absorber--

[0230] The methacrylic resin composition of the present embodiment may contain a UV absorber.

[0231] There is no particular limitation on the ultraviolet absorber, but preferably an ultraviolet absorber having a maximum absorption wavelength in the range of 280 to 380 nm, for example, benzotriazole compounds, benzotriazine compounds, benzophenone compounds, oxybenzophenone compounds, benzoate compounds, phenol compounds, oxazole compounds, cyanoacrylate compounds, benzoxazinone compounds, etc.

[0232] These ultraviolet absorbers may be used alone or in combination of two or more.

[0233] As the ultraviolet absorber, benzotriazole compounds and benzotriazine compounds having a molecular weight of 400 or more are preferred, particularly from the viewpoint of compatibility with the resin and volatility during heating. Furthermore, benzotriazine compounds are particularly preferred from the viewpoint of suppressing decomposition of the ultraviolet absorber itself due to heating during extrusion processing.

[0234] The content of the ultraviolet absorber is not particularly limited as long as it does not hinder heat resistance, moisture and heat resistance, thermal stability and molding processability and is an amount that can exert the effects of the present invention. It is preferably 0.1 to 5 parts by mass, preferably 0.2 to 4 parts by mass, more preferably 0.25 to 3 parts by mass, and further preferably 0.3 to 3 parts by mass relative to 100 parts by mass of the methacrylic resin. When it is within this range, the balance of ultraviolet absorption performance, moldability, etc. is excellent.

[0235] --Release Agent--

[0236] The methacrylic resin composition of the present embodiment may contain a release agent. The release agent is not limited to the following substances, and examples thereof include fatty acid esters, fatty acid amides, fatty acid metal salts, hydrocarbon lubricants, alcohol lubricants, polyalkylene glycols, carboxylates, hydrocarbon paraffin-based mineral oils, and the like.

[0237] These release agents may be used alone or in combination of two or more.

[0238] The fatty acid ester that can be used as the release agent is not particularly limited, and conventionally known fatty acid esters can be used.

[0239] As fatty acid esters, for example, ester compounds of fatty acids having 12 to 32 carbon atoms such as lauric acid, palmitic acid, margaric acid, stearic acid, oleic acid, arachidic acid, and behenic acid and monohydric aliphatic alcohols such as palmityl alcohol, stearyl alcohol, and behenyl alcohol, and polyhydric aliphatic alcohols such as glycerol, pentaerythritol, dipentaerythritol, and sorbitan; and complex ester compounds of fatty acids and polybasic organic acids with monohydric aliphatic alcohols or polyhydric aliphatic alcohols, etc. can be used.

[0240] Examples of such fatty acid ester lubricants include cetyl palmitate, butyl stearate, stearyl stearate, stearyl citrate, glyceryl monocaprylate, glyceryl monocaprate, glyceryl monolaurate, glyceryl monopalmitate, glyceryl dipalmitate, glyceryl monostearate, glyceryl distearate, glyceryl tristearate, glyceryl monooleate, glyceryl dioleate, glyceryl trioleate, glyceryl monolinoleate, glyceryl monobehenate, glyceryl mono-12-hydroxystearate, glyceryl di-12-hydroxystearate, glyceryl tri-12-hydroxystearate, glyceryl diacetyl monostearate, glyceryl citric acid fatty acid esters, pentaerythritol adipic acid stearate, montanic acid partially saponified ester, pentaerythritol tetrastearate, dipentaerythritol hexastearate, and sorbitan tristearate.

[0241] These fatty acid ester lubricants may be used alone or in combination of two or more.

[0242] Examples of commercially available products include RIKEMAL series, POEM series, RIKESTER series, and RIKEMASTER series manufactured by Riken Vitamin Co., Ltd. and EXCEL series, RHEODOL series, EXCEPARL series, and COCONARD series manufactured by Kao Corporation. More specifically, RIKEMAL S-100, RIKEMAL H-100, POEM V-100, RIKEMAL B-100, RIKEMAL HC-100, RIKEMAL S-200, POEM B-200, RIKESTER EW-200, RIKESTER EW-400, EXCEL S-95, and RHEODOL MS-50 may be mentioned.

[0243] The content of the release agent can be any amount as long as the effect as the release agent can be obtained. In the case of an excessive content, there is a concern that problems such as extrusion failure due to bleeding or screw slippage may occur during processing. Therefore, the content of the release agent is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, further preferably 1 part by mass or less, further preferably 0.8 parts by mass or less, further preferably 0.01 to 0.8 parts by mass, and particularly preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the methacrylic resin. When added in the above range, there is a tendency to suppress poor demolding during injection molding in addition to suppressing the decrease in transparency caused by the addition of the release agent.

[0244] --Other thermoplastic resins--

[0245] The methacrylic resin composition of the present embodiment may further contain other thermoplastic resins other than the methacrylic resin for the purpose of adjusting the birefringence and improving the flexibility within a range not impairing the purpose of the present invention.

[0246] As other thermoplastic resins, for example, polyacrylates such as polybutyl acrylate; styrene polymers such as polystyrene, styrene-methyl methacrylate copolymer, styrene-butyl acrylate copolymer, styrene-acrylonitrile copolymer, acrylonitrile-butadiene-styrene block copolymer; in addition, for example, 3-4 layer structure acrylic rubber particles described in Japanese Unexamined Patent Publication No. 59-202213, Japanese Unexamined Patent Publication No. 63-27516, Japanese Unexamined Patent Publication No. 51-129449, Japanese Unexamined Patent Publication No. 52-56150, etc.; rubber polymers disclosed in Japanese Unexamined Patent Publication No. 60-17406 and Japanese Unexamined Patent Publication No. 8-245854; methacrylic rubber-containing graft copolymer particles obtained by multi-stage polymerization described in International Publication No. 2014-002491, etc.

[0247] Among them, from the viewpoint of obtaining good optical and mechanical properties, preferred are styrene-acrylonitrile copolymers and rubber-containing graft copolymer particles having a graft portion in the surface layer, wherein the graft portion is composed of a composition compatible with a methacrylic resin containing a structural unit (X) having a ring structure in the main chain.

[0248] The average particle size of the aforementioned acrylic rubber particles, methacrylic rubber-containing graft copolymer particles, and rubber polymer is preferably 0.03 to 1 μm, more preferably 0.05 to 0.5 μm, from the viewpoint of improving the impact strength and optical properties of the molded product obtained from the composition of this embodiment.

[0249] As content of another thermoplastic resin, when methacrylic resin is 100 parts by mass, it is preferably 0 to 50 parts by mass, and more preferably 0 to 25 parts by mass.

[0250] From the viewpoint of heat resistance, the glass transition temperature (Tg) of the methacrylic resin composition used in the present embodiment is 115 to 160°C. If the glass transition temperature (Tg) is above 115°C, the occurrence of warping and convex deformation is reduced in reliability tests such as high temperature aging tests, and there is a tendency not to have an adverse effect on optical properties. On the other hand, if the glass transition temperature (Tg) is below 160°C, melt processing under extreme high temperature conditions can be avoided, thermal decomposition of resins, etc. can be suppressed, and there is a tendency to obtain a plate-shaped molded product with good appearance. From the viewpoint of further obtaining the above-mentioned effects, the glass transition temperature (Tg) is preferably 115 to 150°C, more preferably 120 to 145°C, and particularly preferably 120 to 140°C.

[0251] In addition, the glass transition temperature can be measured by the midpoint method in accordance with JIS-K7121, and specifically, can be measured by the method described in the examples described later.

[0252] It is preferred that the methacrylic resin composition used in this embodiment has a relatively low viscosity and a moderately high fluidity when injected to improve the transferability of fine convex shapes. -1 Under the conditions of , the melt viscosity is 20 to 235 Pa·sec, preferably 20 to 230 Pa·sec, more preferably 30 to 180 Pa·sec, and particularly preferably 50 to 150 Pa·sec. If the melt viscosity is 20 Pa·sec or more, it is easy to control the flow of the resin during injection, and there is a tendency to easily mold the target shape. On the other hand, if the melt viscosity is 235 Pa·sec or less, the resin has good fluidity and good processability, and there is a tendency that molding defects such as poor filling are less likely to occur.

[0253] In addition, the melt viscosity is a value measured according to JIS-K7199, and can be specifically measured by the method described in the Examples mentioned later.

[0254] The methacrylic resin composition used in this embodiment preferably has a large tensile elongation at break to avoid cracking during demolding and resin residue in the mold. The tensile elongation at break is preferably 1.2% or more, more preferably 1.5% or more, and even more preferably 2.0% or more.

[0255] In addition, the tensile elongation at break is a value measured in accordance with ISO527, and can be specifically measured by the method described in the examples described later.

[0256] In order to suppress thermal decomposition during molding, the terminal double bond ratio of the methacrylic resin composition used in the present embodiment is preferably 5.0% or less, more preferably 4.0% or less, and further preferably 3.5% or less. When the terminal double bond ratio of the methacrylic resin composition is within the above range, the yellowness is small, the occurrence of molding defects such as silver white is reduced, and a molded product with good appearance tends to be obtained.

[0257] In addition, specifically, the terminal double bond ratio of the methacrylic resin composition can be measured by the method described in the Examples mentioned later.

[0258] For the methacrylic resin composition contained in the plate-shaped molded product of the present embodiment, the weight average molecular weight (Mw) of polymethyl methacrylate conversion measured by gel permeation chromatography (GPC) is preferably in the range of 90,000 to 170,000, more preferably in the range of 95,000 to 160,000, and further preferably in the range of 100,000 to 150,000. If Mw is 90,000 or more, the generation of cracks is reduced during molding, and there is a tendency to obtain a plate-shaped molded product with good appearance. On the other hand, if Mw is 170,000 or less, the balance between mechanical strength and fluidity is excellent, and there is a tendency to easily obtain a plate-shaped molded product with good appearance during molding.

[0259] In addition, specifically, the weight average molecular weight of the methacrylic resin composition can be measured by the method described in the Examples mentioned later.

[0260] (Method for producing methacrylic resin composition)

[0261] As a method for producing the methacrylic resin composition of the present embodiment, for example, there can be mentioned a method of kneading using a kneading machine such as an extruder, a heating roll, a kneader, a tumble mixer, or a Banbury mixer. Among them, kneading using an extruder is preferred from the viewpoint of productivity.

[0262] The kneading temperature may be set according to the preferred processing temperature of the polymer constituting the methacrylic resin and other resins to be mixed, and is generally in the range of 140 to 300° C., preferably 180 to 280° C. In order to reduce volatile components, it is preferred to provide a vent in the extruder.

[0263] Example

[0264] Hereinafter, specific examples and comparative examples will be given for explanation, but the present invention is not limited thereto.

[0265] [raw material]

[0266] The raw materials used in the following Examples and Comparative Examples are as follows.

[0267] [[Monomers constituting methacrylic resin]]

[0268] ·Methyl methacrylate (MMA): manufactured by Asahi Kasei Co., Ltd.

[0269] · N-phenylmaleimide (PMI): manufactured by Nippon Shokubai Co., Ltd.

[0270] ·N-Cyclohexylmaleimide (CMI): manufactured by Nippon Shokubai Co., Ltd.

[0271] Styrene: manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0272] · Methyl 2-(hydroxymethyl)acrylate (MHMA): manufactured by Combi-Blocks.

[0273] [[Organic solvents]]

[0274] ·Metaxylene (mXy): manufactured by Mitsubishi Gas Chemical Co., Ltd.

[0275] Methyl isobutyrate: manufactured by Kanto Chemical Co., Ltd.

[0276] Toluene: manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0277] [[Polymerization initiator]]

[0278] 1,1-Di(tert-butylperoxy)cyclohexane: manufactured by NOF Corporation.

[0279] · Tert-amyl peroxy-2-ethylhexanoate: “Luperox 575” manufactured by Arkema GIFA Co., Ltd.

[0280] · Tert-amyl peroxyisononanoate: manufactured by Arkema Gifu Co., Ltd.

[0281] [[Chain transfer agent]]

[0282] n-Octylmercaptan: manufactured by Chevron Phillips Chemical Company.

[0283] · n-Dodecyl mercaptan: manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0284] [[additive]]

[0285] Pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]: "Irganox 1010" manufactured by BASF.

[0286] Tris(2,4-di-tert-butylphenyl)phosphite: “Irgafos 168” manufactured by BASF.

[0287] ·RIKEMAL H-100: manufactured by Riken Vitamin Co., Ltd.

[0288] ADK STAB 2112: Made by ADEKA Co., Ltd. of Japan.

[0289] Stearyl phosphate / distearyl phosphate mixture: manufactured by Sakai Chemical Industry Co., Ltd. ADK STAB PEP-36: manufactured by ADEKA Corporation of Japan.

[0290] Octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionate: "Irganox 1076" manufactured by BASF.

[0291] ·Monomethylamine: manufactured by Mitsubishi Gas Chemical Co., Ltd.

[0292] Dimethyl carbonate: manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0293] Triethylamine: manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0294] (Evaluation of properties of methacrylic resin and methacrylic resin composition)

[0295] The following describes a method for measuring the properties of the methacrylic resin composition.

[0296] (1) Determination of glass transition temperature

[0297] The glass transition temperature of the methacrylic resin composition was measured in accordance with JIS-K7121.

[0298] A differential scanning calorimeter (DSC8000, manufactured by PerkinElmer Japan) was used under the condition of a nitrogen flow rate of 25 mL / min. Here, the temperature was increased from room temperature (23°C) to 200°C at a rate of 10°C / min (primary heating), and maintained at 200°C for 5 minutes to completely melt the sample. Then, the temperature was lowered from 200°C to 40°C at a rate of 10°C / min, and maintained at 40°C for 5 minutes. Furthermore, the temperature was increased again under the above-mentioned heating conditions (secondary heating). In the DSC curve drawn during this period, the intersection of the curve of the step-shaped change part during the secondary heating and the straight line with an equal distance from each baseline extension line in the vertical axis direction (midpoint glass transition temperature) was measured as the glass transition temperature (Tg) (°C).

[0299] (2) Determination of melt viscosity

[0300] A double capillary rheometer (manufactured by NETZSCH (Rosand)) was used under the conditions of JIS-K7199 at a temperature of 270°C and a shear rate of 1000 sec. -1 The melt viscosity (Pa·sec) of the methacrylic resin composition was measured under the conditions of a 100% mol / l capillary die diameter of 1 mm.

[0301] (3) Determination of tensile elongation at break

[0302] The pellets of the methacrylic resin composition were dried at 80 to 100° C. for 24 hours and injection molded using an injection molding machine (manufactured by Toshiba Machine Co., Ltd., EX-100SX) in accordance with JIS-K6717 to prepare a 4.0 mm thick ISO3167 A-type dumbbell test piece. The test piece was subjected to a tensile test using a low-load universal material testing machine (manufactured by Instron) at a measurement temperature of 23° C. and a crosshead speed of 5 mm / min in accordance with ISO527. The measurement was performed 5 times, and the elongation between the clamps at the time of tensile fracture was measured, and the average value was calculated as the tensile fracture elongation (%).

[0303] (4) Determination of terminal double bond rate

[0304] In order to measure the terminal double bond ratio of the methacrylic resin composition, dissolution and reprecipitation were performed as a pretreatment to remove low molecular weight substances.

[0305] Specifically, 500 mg of the pellets of the methacrylic resin composition were weighed and dissolved in 5 mL of chloroform, and then 30 mL of methanol was added to precipitate the polymer. The precipitated polymer was recovered and dried in a vacuum dryer at 40°C for 5 hours. The sample was dissolved in CDCl3 to a concentration of 100 mg / mL and used as an NMR measurement sample. The measurement was performed under the following measurement conditions: 1H-NMR, the terminal double bond ratio (%) was calculated by the following calculation formula (1) using the integrated intensity of the peak of the terminal double bond part (resonance frequency 5.5 ppm and 6.1 ppm), the integrated intensity of the peak of the main chain methoxy group in the MMA unit (resonance frequency 3.6 ppm), and the number average molecular weight (Mn) of the methacrylic resin composition measured by the method described later.

[0306]

[0307] [NMR measurement conditions]

[0308] Apparatus: AVANCEIII 500HD Prodigy (Bruker BioSpin, Switzerland).

[0309] Observation frequency: 500MHz( 1 H).

[0310] Number of integral operations: 10,000 times.

[0311] Reference substance: 0 ppm (tetramethylsilane).

[0312] Measurement temperature: 298K

[0313] (5) Measurement of weight average molecular weight and number average molecular weight of methacrylic resin composition

[0314] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin composition were measured using the following apparatus and conditions.

[0315] ·Measurement apparatus: Gel permeation chromatograph manufactured by Tosoh Corporation (HLC-8320GPC)

[0316] ·Measurement conditions:

[0317] Chromatographic columns: One TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgelSuperH2500 were connected in series in this order and used.

[0318] Column temperature: 40°C.

[0319] The developing solvent was tetrahydrofuran, and the flow rate was 0.6 mL / min. As an internal standard, 0.1 g / L of 2,6-di-tert-butyl-4-methylphenol (BHT) was added.

[0320] Detector: RI (refractive index) detector.

[0321] Detection sensitivity: 3.0mV / min.

[0322] Sample: 20 mL of tetrahydrofuran solution of 0.02 g of a methacrylic resin composition.

[0323] Injection volume: 10 μL.

[0324] Standard samples for calibration curve: The following 10 types of polymethyl methacrylates having known monodisperse weight peak molecular weight and different molecular weights (manufactured by Polymer Laboratories; PMMA Calibration Kit MM-10) were used.

[0325] Weight peak molecular weight (Mp)

[0326] Standard sample 1 1916000 Standard sample 2 625500 Standard sample 3 298900 Standard sample 4 138600 Standard sample 5 60150 Standard sample 6 27600 Standard sample 7 10290 Standard sample 8 5000 Standard sample 9 2810 Standard sample 10 850

[0327] Under the above conditions, the RI detection intensity relative to the elution time of the methacrylic resin composition was measured.

[0328] As described above, the weight average molecular weight (Mw) and the number average molecular weight (Mn) of the methacrylic resin composition are determined based on each calibration curve obtained by measuring the standard sample for calibration curve.

[0329] (Evaluation method for molded products)

[0330] The following describes the evaluation methods related to the plate-shaped molded products.

[0331] (1) Measurement of the height and pitch of convex shapes of molded products

[0332] The cross section obtained by cutting the plate-like molded product in a direction perpendicular to the main surface (thickness direction) was observed using a digital microscope (Keyence Corporation, Japan, VHX-1000). The height and spacing of the convex shapes formed on the first main surface of the molded product were measured based on the obtained observation image, and the average values ​​of the five convex shapes were recorded as the height a and the spacing b in Table 1.

[0333] (2) Determination of the filling degree of the convex shape of the molded product

[0334] The cross section obtained by cutting the plate-like molded product in a direction perpendicular to the main surface (thickness direction) was observed using a digital microscope (Keyence Corporation, Japan, VHX-1000). The height a of the convex shape formed on the first main surface of the molded product was obtained, and the filling degree defined as the ratio of the height a to the depth of the concave shape in the first mold used to shape the convex shape was derived by the following calculation formula, and the average value of the four points was recorded as the filling degree value in Table 1.

[0335] In fact, if the filling degree is 0.92 or more, it can be judged that it is suitable as a molded product to which a convex shape is transferred.

[0336] (Filling degree) = (height a of the convex shape of the molded product) / (depth of the concave shape of the mold)

[0337] (3) Determination of warpage of molded products

[0338] The plate-shaped molded product is placed on a metal platform with the first main surface having a convex shape as the upper surface, and the periphery of the molded product is evenly divided at four points. A thickness gauge is used to measure the thickness of the four points ( Figure 1 The gap between the molded product and the platform was measured at four points (point 15a, point 15b, point 15c, and point 15d in (A), and the value at the location with the largest gap (warpage) was taken as the warpage (mm) of the molded product.

[0339] It should be noted that in the case of a molded product having a concave-convex portion for connecting to other parts on the back side (second main surface) of the first main surface of the molded product, trimming is performed so that only the portion that does not include the concave-convex portion for connection remains, and the cross section is polished with sandpaper, and then the warping amount is measured.

[0340] In essence, Figure 1 , Figure 3 In the plate-like molded product of the shape shown, if the amount of warpage is 0.4 mm or less, it can be judged that the dimensional accuracy as the molded product is within a preferred range.

[0341] (4) Evaluation of the appearance of molded products

[0342] The plate-shaped molded product was visually observed to observe uneven gloss on the first main surface due to poor filling of the resin on the fine convex shape forming surface of the first mold, poor appearance and yellowing accompanied by undulations on the second main surface.

[0343] If there is a poorly filled area with resin, it can be confirmed by the shape of the local defect. In addition, for the undulation of the second main surface, for example, when confirming the reflected image when a fluorescent lamp housed in a rectangular shell with a longer side is irradiated from above, the quality of the plane can be judged by confirming whether the straight line is deformed. In addition, when the yellowness index (YI) of the molded product measured by the measurement method described later is less than 7.0, it is judged that the yellowing is suppressed, when the YI is 7.0 to 10.0, it is judged as a slightly yellowed state, and when it is greater than 10.0, it is judged as a very yellowed state.

[0344] The case where neither uneven gloss of the first main surface nor undulation of the second main surface was observed and yellowing of the molded product was suppressed was evaluated as "A", the case where any one of uneven gloss of the first main surface, undulation of the second main surface, and yellowing of the molded product was observed was evaluated as "B", and the case where any two or more of uneven gloss of the first main surface, undulation of the second main surface, and yellowing of the molded product were observed was evaluated as "C".

[0345] (5) Measurement of in-plane phase difference of molded products

[0346] The plate-like molded product is placed in a culture dish set on a measuring table of PA-300-L (manufactured by Photonic-lattice Co.) in such a way that the first main surface is located on the upper surface. Then, a low-viscosity liquid (contact liquid manufactured by Shimadzu Corporation) having a refractive index close to that of the methacrylic resin used and which does not penetrate into the methacrylic resin is added to the culture dish in such a way that it fills up to the top of the convex shape of the molded product. The first main surface of the molded product is immersed in the liquid, and the liquid surface of the liquid is flat and has no height difference. In this state, the in-plane phase difference distribution at a wavelength of 520nm is directly measured. The area where the convex shape is formed is determined (refer to Figure 1 (A) Figure 3 The average value of the absolute values ​​of the in-plane retardation (Re) in (A)) was taken as the measured value of the retardation (nm).

[0347] The value of birefringence is set in a range that does not adversely affect the optical characteristics, and the in-plane retardation is preferably less than 100 nm.

[0348] (6) Projected area of ​​the first main surface

[0349] The plate-shaped molded product is placed so that the first main surface is the upper surface, and the first main surface is observed from above to obtain the area of ​​the first main surface in plan view, which is taken as the projected area (cm 2 ).

[0350] (7) Determination of the amount of methyl methacrylate (MMA) in molded products

[0351] The amount of methyl methacrylate (MMA) contained in the plate-shaped molded product was measured.

[0352] [Sample preparation]

[0353] The sample was cut out from the opposite side of the gate of the plate-shaped molded product, 0.36 g of which was accurately weighed, and 2.5000 g of internal standard solution (a solution prepared by dissolving 0.9100 g of decane in 70.0000 g of chloroform) was added, and the mixture was stirred thoroughly to dissolve. After dissolution, 20.0000 g of isopropanol was added, stirred, and then allowed to stand to reprecipitate the copolymer. The supernatant solution was collected and subjected to gas chromatography under the following measurement conditions.

[0354] [Measurement conditions]

[0355] Apparatus: GC-2025 (manufactured by Shimadzu Corporation).

[0356] column

[0357] Column name: Zebron ZB-1 (manufactured by Phenomenex).

[0358] P / N:7HM-G001-11.

[0359] Length:30.0mm.

[0360] Inner diameter: 0.32mm ID.

[0361] Film thickness: 0.25μm.

[0362] Column oven conditions

[0363] Initial temperature: 45°C (maintained for 5 minutes).

[0364] Heating rate: 20.00℃ / min.

[0365] Final temperature: 300.0°C (hold 12.25 minutes).

[0366] Sample gasification conditions

[0367] Vaporization chamber temperature: 210.0℃.

[0368] Carrier gas: Helium.

[0369] Pressure: 70.1kPa.

[0370] Total flow rate: 93.2 mL / min.

[0371] Column flow rate: 2.20 mL / min.

[0372] Line speed: 71.0 cm / sec.

[0373] Purge flow rate: 3.0 mL / min.

[0374] Split ratio: 40.

[0375] Detector (FID) conditions

[0376] Detector temperature: 300.0°C.

[0377] Sampling rate: 40msec.

[0378] Make-up gas: N2.

[0379] Supplement flow rate: 30.0mL / min.

[0380] H2 flow rate: 40.0 mL / min.

[0381] Air flow rate: 400.0 mL / min.

[0382] Autosampler conditions

[0383] Injection volume: 1.0 μL.

[0384] (8) Determination of yellowness index (YI) of molded products

[0385] The plate-shaped molded product was crushed and dissolved in chloroform for high performance liquid chromatography (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to prepare a 12% by mass chloroform solution. The solution was placed in a quartz cuvette with an optical path length of 10 cm to prepare a sample for measurement. Then, using an ultraviolet visible spectrophotometer UV-2600 (manufactured by Shimadzu Corporation), a cuvette of chloroform for high performance liquid chromatography (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was placed in a quartz cuvette with an optical path length of 10 cm as a reference cuvette, and the above-mentioned 12% by mass chloroform solution was set as a measurement cuvette to measure the yellowness index (YI).

[0386] [Measurement conditions]

[0387] Measured value: transmitted light.

[0388] Measuring range: 0.0~100.0.

[0389] Wavelength range: 780~360nm.

[0390] Scanning speed: high speed.

[0391] Slit width: 2.0nm.

[0392] Sampling spacing: 2.0nm.

[0393] Lighting: C light source.

[0394] Viewing angle:10°.

[0395] Synthesis Example 1 [Methacrylic Resin Composition A]

[0396] 318.7 kg of methyl methacrylate (hereinafter referred to as MMA), 35.5 g of N-phenylmaleimide (hereinafter referred to as PMI), 63.7 kg of N-cyclohexylmaleimide (hereinafter referred to as CMI), 0.341 kg of n-octyl mercaptan as a chain transfer agent, and 225.1 kg of meta-xylene (hereinafter referred to as mXy) ​​were weighed and added to a 1.25 m3 / 450 tumbler equipped with a jacketed temperature control device and a stirring blade. 3 The mixture was placed in a reactor and stirred to obtain a mixed monomer solution.

[0397] Then, 116.9 kg of mXy was weighed and added to tank 1 to prepare for solvent replenishment.

[0398] Furthermore, 104.5 kg of MMA and 85.5 kg of mXy were weighed and placed in tank 2, and stirred to obtain a supplementary MMA solution.

[0399] The internal liquid of the reactor was bubbled with nitrogen at a rate of 30 L / min for 1 hour, and nitrogen was bubbled with nitrogen at a rate of 10 L / min for 30 minutes in each of the tanks 1 and 2 to remove dissolved oxygen.

[0400] Then, steam was blown into the jacket to raise the temperature of the solution in the reactor to 125°C, and a polymerization initiator solution was added at a rate of 1 kg / hour while stirring at 50 rpm, in which 0.457 kg of 1,1-di(tert-butylperoxy)cyclohexane was dissolved in 2.67 kg of mXy, thereby starting polymerization. It should be noted that during the polymerization, the temperature of the solution in the reactor was controlled at 125±2°C by adjusting the temperature of the jacket. 30 minutes after the start of the polymerization, the addition rate of the polymerization initiator solution was reduced to 0.25 kg / hour, and mXy for 3.5 hours was added from tank 1 at 29.24 kg / hour.

[0401] Then, 4 hours after the start of the polymerization, the addition rate of the polymerization initiator solution was increased to 0.75 kg / hour, and the replenishing MMA solution was added from the tank 2 at 95 kg / hour for 2 hours.

[0402] Furthermore, 6 hours after the start of the polymerization, the addition rate of the polymerization initiator solution was reduced to 0.25 kg / hour, and 7 hours after the start of the polymerization, the addition was stopped.

[0403] After 8 hours from the start of polymerization, a polymerization solution containing a methacrylic resin was obtained, to which 0.261 kg of Irganox 1010 as an antioxidant, 0.784 kg of Irgafos 168, and 0.784 kg of RIKEMAL H-100 as a release agent were added.

[0404] Then, the obtained polymer solution was supplied to a concentrator composed of a tubular heat exchanger and a vaporizer preheated to 250° C. for devolatilization. The vacuum degree of the vaporizer was set to 10 to 15 Torr. The resin flowing down from the vaporizer was discharged by a screw pump, extruded from a strand die, water-cooled, and pelletized to obtain a methacrylic resin composition A having an N-substituted maleimide structural unit.

[0405] Synthesis Example 2 [Methacrylic Resin Composition B]

[0406] A monomer composition consisting of 60.000 mol% of methyl methacrylate, 39.998 mol% of styrene, and 0.002 mol% of tert-amyl peroxy-2-ethylhexanoate as a polymerization initiator was continuously supplied at 1 kg / h to a 10L complete mixing tank equipped with spiral ribbon blades, and continuous polymerization was carried out with an average residence time of 2.5 hours and a polymerization temperature of 150°C. The liquid was continuously extracted from the bottom of the polymerization tank in a constant manner and supplied to a concentrator consisting of a tubular heat exchanger and a vaporization tank for devolatilization. The vacuum degree of the vaporization tank was set to 10 to 15 Torr. The resin flowing down from the vaporization tank was discharged with a screw pump, extruded from a wire drawing die and water-cooled, and then pelletized and introduced into a desolventizing device to obtain a granular methyl methacrylate-styrene copolymer.

[0407] The copolymer was dissolved in methyl isobutyrate to prepare a 10% by mass methyl isobutyrate solution. 500 parts by mass of a 10% by mass methyl isobutyrate solution of the copolymer and 1 part by mass of 10% Pd / C (manufactured by NECHEMCAT CORPORATION) as a hydrogenation catalyst were added to a 1000 mL autoclave apparatus, and the mixture was kept at a hydrogen pressure of 9 MPa and 200° C. for 15 hours to hydrogenate the aromatic double bonds of the styrene portion of the copolymer. The hydrogenation catalyst was removed by a filter, 0.05 parts by mass of RIKEMAL H-100 was added to the polymer solution and mixed, and then supplied to a concentrator consisting of a tubular heat exchanger and a vaporizer tank for devolatilization. The vacuum degree of the vaporizer tank was set to a condition of 10 to 15 Torr. The resin flowing down from the vaporizer tank was discharged by a gear pump, extruded from a wire drawing die head and water-cooled, and then pelletized to obtain a methacrylic resin composition B.

[0408] Synthesis Example 3 [Methacrylic Resin Composition C]

[0409] Into a 30 L reactor equipped with a stirring device equipped with a paddle-shaped blade, a temperature sensor, a cooling pipe, and a nitrogen introduction pipe, 5.0 kg of methyl methacrylate, 1.25 kg of methyl 2-(hydroxymethyl)acrylate, 0.025 parts by mass of n-dodecyl mercaptan as a chain transfer agent relative to 100 parts by mass of the total amount of all monomers, 0.025 parts of ADK STAB 2112, and 6.25 kg of toluene were charged, nitrogen was introduced therein, and the temperature was raised to 105° C. while stirring.

[0410] 0.05 parts by mass of tert-amyl peroxyisononanoate relative to 100 parts by mass of the total amount of all monomers was added to the polymerization tank while refluxing, and then 0.1 parts by mass of tert-amyl peroxyisononanoate was added dropwise over 2 hours, and polymerization was carried out at a polymerization temperature of 105 to 110° C. under reflux conditions, and the polymerization reaction was further carried out for 6 hours.

[0411] 6.3 g of a stearyl phosphate / distearyl phosphate mixture was added to the obtained polymer solution, and a cyclocondensation reaction was performed at 90 to 110° C. for 5 hours. Then, 0.10 parts by mass of RIKEMAL H-100 was added based on 100 parts by mass of the total monomer amount, and the mixture was stirred and mixed.

[0412] Use a model with four front exhaust ports and one rear exhaust port The obtained polymerization liquid was subjected to cyclocondensation reaction and devolatilization treatment in a devolatilizing extruder at 120 rpm and 2.2 kg / hour in terms of resin amount, thereby obtaining pellets of a methacrylic resin composition C.

[0413] Synthesis Example 4 [Methacrylic Resin Composition D]

[0414] Polymethyl methacrylate was imidized with monomethylamine using a co-rotating twin-screw extruder to obtain a methacrylic resin composition having a glutarimide structure.

[0415] A co-rotating twin-shaft extruder with a screw diameter of 40 mm was used, the extruder barrel temperature was set to 275°C, the screw speed was set to 150 rpm, and polymethyl methacrylate with a weight average molecular weight of 108,000 containing 0.1 parts by mass of RIKEMAL H-100 was supplied from the hopper at 20 kg / hour when the mass of the total polymer was set to 100 parts by mass, and nitrogen was introduced into the extruder at a flow rate of 200 mL / min. After the resin was melted and filled by the kneading block, 1.8 parts by mass of monomethylamine was injected from the nozzle relative to 100 parts by mass of the raw resin to carry out the imidization reaction. A reverse thread was placed at the end of the reaction area (before the exhaust port) and filled with resin. The pressure at the exhaust port was reduced to 50 Torr to remove the by-products and excess monomethylamine after the reaction. The resin coming out of the die head set at the outlet of the extruder in strands was cooled in a water tank and granulated with a granulator to obtain an imide resin.

[0416] Then, a co-rotating twin-shaft extruder with a screw diameter of 40 mm was used, the extruder barrel temperature was set to 255°C, the screw speed was set to 150 rpm, and the obtained imide resin was supplied at 20 kg / hour. After the resin was melted and filled by the kneading block, a mixed solution of dimethyl carbonate and triethylamine as an esterifying agent was injected from the nozzle to reduce the carboxylic acid group in the resin. Relative to 100 parts by mass of the imide resin, dimethyl carbonate was 3.2 parts by mass and triethylamine was 0.8 parts by mass. The pressure at the exhaust port was reduced to 50 Torr to remove the by-products and excess dimethyl carbonate after the reaction. The resin coming out of the die head arranged at the outlet of the extruder in strands was cooled in a water tank and granulated with a granulator to obtain a methacrylic resin composition D having a glutarimide structure.

[0417] Synthesis Example 5 [Methacrylic Resin Composition E]

[0418] A methacrylic resin composition E was obtained by polymerization in the same manner as in Synthesis Example 1 except that the amount of n-octyl mercaptan as a chain transfer agent was changed to 0.708 kg.

[0419] Synthesis Example 6 [Methacrylic Resin Composition F]

[0420] 291.5 kg of MMA, 44.0 kg of PMI, 104.5 kg of CMI, 0.20 kg of n-octyl mercaptan as a chain transfer agent, and 247.0 kg of mXy were weighed and added to a 1.25 m3 / 450 t / cm3 reactor equipped with a jacketed temperature control device and a stirring blade. 3 The mixture was placed in a reactor and stirred to obtain a mixed monomer solution.

[0421] Then, 123.0 kg of mXy was measured and added to tank 1.

[0422] Furthermore, 110.0 kg of MMA and 80.0 kg of mXy were weighed and placed in tank 2, and stirred to prepare a monomer solution for replenishment.

[0423] The internal liquid of the reactor was bubbled with nitrogen at a rate of 30 L / min for 1 hour, and nitrogen was bubbled with nitrogen at a rate of 10 L / min for 30 minutes in each of the tanks 1 and 2 to remove dissolved oxygen.

[0424] Then, steam was blown into the jacket to raise the temperature of the solution in the reactor to 124°C, and a polymerization initiator solution prepared by dissolving 0.35 kg of 1,1-di(tert-butylperoxy)cyclohexane in 4.652 kg of mXy was added at a rate of 1 kg / hour while stirring at 50 rpm to start polymerization, and mXy was added from tank 1 at a rate of 30.75 kg / hour for 4 hours.

[0425] During the polymerization, the temperature of the solution in the reactor was controlled at 124±2° C. by temperature regulation using a jacket.

[0426] Then, during the period from 4 hours to 6 hours later, a monomer solution containing MMA was added from the tank 2 at a rate of 95 kg / hour.

[0427] Furthermore, for the polymerization initiator solution, the addition rate was reduced to 0.25 kg / hour 0.5 hour after the start of polymerization, the addition rate was reduced to 0.75 kg / hour 4 hours later, and the addition rate was reduced to 0.5 kg / hour 6 hours later. The addition of the polymerization initiator solution was stopped 7 hours after the start of polymerization, and the polymerization was continued for another 3 hours to obtain a polymerization solution containing a methacrylic resin having a ring structural unit in the main chain.

[0428] To the polymerization solution were added 0.83 kg of ADK STAB PEP-36, 0.28 kg of Irgafos 168, 0.44 kg of Irganox 1076, and 1.10 kg of RIKEMAL H-100 under stirring.

[0429] Then, the obtained polymer solution was supplied to a concentrator consisting of a tubular heat exchanger and a vaporizer tank preheated to 260° C. for devolatilization. The vacuum degree of the vaporizer tank was set to 10 to 15 Torr. The resin flowing down from the vaporizer tank was discharged by a screw pump, extruded from a wire drawing die, water-cooled, and pelletized to obtain a methacrylic resin F having an N-substituted maleimide structural unit.

[0430] (Examples 1 to 3)

[0431] Molding of plate-shaped molded products with a convex shape on one main surface

[0432] Using the methacrylic resin composition A obtained in Synthesis Example 1, injection molding was performed by an injection molding machine (manufactured by FANUC, Japan, α-S250iA). As a mold, an embedded mold consisting of a mold (first mold) on one side of the main surface forming a triangular pyramidal convex shape with a convex shape height a=400μm and a spacing b=300μm and a mold (second mold) on one side of the main surface forming a plane, and a heater line embedded inside the mold near the surface forming each main surface, was installed on the injection molding machine. After the surface of the first mold was treated with a fluorine-based release coating, the mold temperature of the first mold was heated to the maximum temperature Tmax recorded in Table 1 at a heating rate of about 3°C / second by heating with a heater, and the mold was closed for injection molding. After the resin was filled into the mold at a barrel temperature of 290°C, the mold temperature of the first mold was cooled to the minimum temperature Tmin recorded in Table 1 at a cooling rate of about 1.2°C / second. After reaching Tmin, it was cooled for 90 seconds. The runner and gate were removed to obtain a plate-shaped molded product having a convex shape on one main surface (length 240 mm, width 230 mm, thickness 2.5 mm, refer to Figure 1 It should be noted that, for the holding pressure, immediately after injection, the first stage was set to 100 MPa to obtain good transfer, and then the holding pressure was set to be lower than the first stage to ease the stress and strain inside the molded product, and the second stage was set to 30 MPa. The evaluation results are shown in Table 1.

[0433] As can be seen from Table 1, in Examples 1 to 3, the filling degree was 0.98 to 0.99, and very excellent results were obtained. In addition, the warpage and appearance were also good.

[0434] (Example 4)

[0435] Using the methacrylic resin composition B obtained in Synthesis Example 2, molding was performed under the same conditions as in Example 1 except that the cylinder temperature was set to 280°C, the maximum temperature Tmax of the first mold was set to 175°C, the minimum temperature Tmin was set to 60°C, the temperature of the second mold was set to 108°C, and the holding pressure of the first stage was set to 95 MPa. The evaluation results are shown in Table 1.

[0436] (Example 5)

[0437] Using the methacrylic resin composition C obtained in Synthesis Example 3, molding was performed under the same conditions as in Example 1 except that the maximum temperature Tmax of the first mold was 190° C., the minimum temperature Tmin was 60° C., and the temperature of the second mold was 108° C. The evaluation results are shown in Table 1.

[0438] (Example 6)

[0439] Molding was performed under the same conditions as in Example 2 except that the methacrylic resin composition D obtained in Synthesis Example 4 was used. The evaluation results are shown in Table 1.

[0440] (Example 7)

[0441] The methacrylic resin composition E obtained in Synthesis Example 5 was used as a mold for a plate-shaped molded product (length 270 mm, width 260 mm, thickness 2.5 mm, refer to FIG. 1 ) having a convex shape of a quadrangular pyramid trapezoid (base 140 μm square, angle between the base and the side surface 85 degrees) with a convex shape height a=400 μm and a pitch b=160 μm on one main surface and a flat main surface on the other main surface. Figure 3 ) and an embedded mold in which a heater wire was embedded in the mold near the surface forming each main surface, molding was performed under the same conditions as in Example 2. The evaluation results are shown in Table 1.

[0442] As can be seen from Table 1, in Example 7, the filling degree was 0.99, which was a very excellent result. In addition, the warpage and appearance were also good.

[0443] (Example 8)

[0444] Molding was performed under the same conditions as in Example 1 except that the methacrylic resin composition A obtained in Synthesis Example 1 was used, an embedded mold for a plate-shaped molded product (150 mm long, 150 mm wide, 2.5 mm thick) having a triangular pyramidal convex shape with a convex shape height a=400 μm and a pitch b=300 μm on one main surface and a flat main surface on the other main surface was used as a mold, and a heater wire was embedded in the mold near the surface forming each main surface. The evaluation results are shown in Table 1.

[0445] (Example 9)

[0446] Using the methacrylic resin composition A obtained in Synthesis Example 1, molding was performed under the same conditions as in Example 1 except that the cylinder temperature was set to 290° C., using an embedded mold for a plate-shaped molded product (240 mm long, 230 mm wide, 2.5 mm thick) having a triangular pyramidal convex shape with a convex shape height a=550 μm and a pitch b=300 μm on one main surface and a flat main surface on the other main surface, and a heater wire was embedded in the mold near the surface forming each main surface. The evaluation results are shown in Table 1.

[0447] (Example 10)

[0448] Molding was performed under the same conditions as in Example 9 except that the methacrylic resin composition E obtained in Synthesis Example 5 was used and the cylinder temperature was set to 270° C. The evaluation results are shown in Table 1.

[0449] (Comparative Example 1)

[0450] Molding was performed under the same conditions as in Example 1 except that heating with a heater was not performed and injection was performed at a mold temperature not higher than the glass transition temperature Tg of the methacrylic resin composition A. The evaluation results are shown in Table 1.

[0451] As a result of the evaluation, it could not be said that the convex shape was sufficiently transferred.

[0452] (Comparative Example 2)

[0453] The molding was performed under the same conditions as in Example 1 except that the cylinder temperature was set to 270° C. and the maximum temperature Tmax of the first mold was set to less than (Tg+40)° C. for injection. The evaluation results are shown in Table 1.

[0454] As a result of the evaluation, the filling degree was 0.83, the warpage amount of the molded product was large, 0.80 mm, and the target molded product could not be obtained.

[0455] (Comparative Example 3)

[0456] The molding was performed under the same conditions as in Example 2 except that the temperature of the second mold was set to less than (Tmax-90)°C for injection. The evaluation results are shown in Table 1.

[0457] As a result of the evaluation, the filling degree was 0.98, which was good, but the warpage of the molded product was large, and the target molded product could not be obtained.

[0458] (Comparative Example 4)

[0459] The molding was performed under the same conditions as in Example 2 except that the temperature of the second mold was set to be higher than (Tmax-65)°C for injection. The evaluation results are shown in Table 1.

[0460] As a result of the evaluation, the filling degree was 0.98, which was good, but the warpage of the molded product was large, and a wavy state was observed on the flat side, and the target molded product could not be obtained.

[0461] (Comparative Example 5)

[0462] Molding was performed under the same conditions as in Example 3 except that the methacrylic resin composition F obtained in Synthesis Example 6 was used. The evaluation results are shown in Table 1.

[0463] As a result of the evaluation, the filling degree of the first main surface was 0.75, which confirmed insufficient filling. The warpage amount of the molded product was also large, 0.90 mm, and it was yellowed, and the target molded product could not be obtained.

[0464] (Comparative Example 6)

[0465] Molding was performed under the same conditions as in Example 9 except that the methacrylic resin composition F obtained in Synthesis Example 6 was used. The evaluation results are shown in Table 1.

[0466] As a result of the evaluation, the filling degree of the first main surface was 0.82, which confirmed insufficient filling. The warpage of the molded product was also large, 1.30 mm, and yellowing occurred, so the target molded product could not be obtained.

[0467] (Comparative Example 7)

[0468] Molding was performed under the same conditions as in Example 1 except that the maximum temperature Tmax of the first mold was set to less than (Tg+40)° C. for injection and the temperature of the second mold was changed to 105° C. The evaluation results are shown in Table 1.

[0469] As a result of the evaluation, the filling degree of the first main surface was 0.82, which confirmed insufficient filling. The warpage amount of the molded product was also large, 1.10 mm, and the target molded product could not be obtained.

[0470] (Comparative Example 8)

[0471] Molding was performed under the same conditions as in Example 1 except that a mold (first mold) was used on one side of the main surface to form a triangular pyramidal fine convex portion with a height a=800μm and a pitch b=300μm, and a mold (second mold) was used on one side of the main surface to form a plane.

[0472] In addition, since a part of the fine convex shape part remained in the mold due to mold release failure during mold release, the measurement was performed using a part where the molded product could be evaluated. The evaluation results are shown in Table 1.

[0473]

[0474] The characteristics of the plate-like molded products having fine convex-shaped portions obtained in Example 1 and Comparative Example 1 when used as light direction converting elements were evaluated.

[0475] like Figure 5As shown in the figure, light incident at an incident angle of 45 degrees to the incident surface (the main surface on the back side of the main surface having the fine convex shape) 81 of the plate-shaped molded product 8 having the fine convex shape is reflected by the inclined surface 83 which forms an angle of 85 degrees with the bottom surface 82, and then refracted from the inclined surface 84 which forms an angle of 65 degrees with the bottom surface 82 and is emitted outward. At this time, the light is emitted from the inclined surface 84 at a refraction angle of 64 degrees, and therefore, the light is emitted at an angle of about 90 degrees to the incident surface 81. That is, it can be said that it is a light direction conversion element that bends the light incident at an incident angle of 45 degrees to the incident surface in a direction perpendicular to the incident surface.

[0476] by Figure 6 The molded article 8 was configured as a light direction conversion element in the configuration shown in the figure, and the clarity of the reflected and transmitted images was evaluated. An LED light source 5 (M530L4, manufactured by Thorlabs) with a collimating lens and a frosted diffusion plate 6 (#240, manufactured by SIGMAKOKI) emitting light at 530 nm was configured, and a USAF target 7 (USAF1951 negative target, manufactured by Edmund, with a target area of ​​about 12 mm) was irradiated from the back. The target was passed through a transmission area 71 (refer to Figure 7 ) is incident from the incident surface 81 of the molded product 8 at an incident angle of 45°, and for the light emitted from the convex shape imparting surface (the main surface having a fine convex shape portion) of the molded product 6, a reflected image (an image formed by light transmitted from the inclined surface 84 after being reflected by the inclined surface 83) is captured using a single-lens reflex camera 9 (E-PL5, manufactured by Olympus Corporation, Japan) arranged at a position 350 mm away from the incident surface 81 in the vertical direction.

[0477] The reflected image observed when the molded product obtained in Example 1 was used was a clear image, but the reflected image observed when the molded product obtained in Comparative Example 1 showed distortion or loss of the target image, resulting in a low clarity.

[0478] Industrial Applicability

[0479] The plate-shaped molded product manufactured by the manufacturing method of the present invention has good appearance and dimensional accuracy, and is therefore suitable for use as various optical parts such as Fresnel lenses, double convex lenses, light guide plates, parts for aerial displays, diffractive optical elements, anti-reflection sheets, anti-glare sheets, and sheets for cell culture.

Claims

1. A method for manufacturing a plate-shaped molded product, characterized in that: The plate-shaped molded product comprises a glass transition temperature Tg of 115 to 160° C., a melt viscosity of 270° C., and a 1000 sec -1 The methacrylic resin composition has a temperature of 20 to 235 Pa·sec under the condition of , wherein the plate-shaped molded product has no bonding interface and is composed of a single resin composition, The plate-shaped molded product has one main surface, namely a first main surface, having a plurality of fine convex shapes, and the other main surface, namely a second main surface, being a flat surface. The height a of the convex shape is 0.5 to 700 μm, and the ratio b / a of the pitch b of the convex shape to the height a of the convex shape is 0.1 to 2.

0. The projected area of ​​the first main surface of the plate-shaped molded product is 225 cm 2 above, The manufacturing method includes performing injection molding using a first mold forming one side of the first main surface and a second mold forming one side of the second main surface, setting the maximum temperature Tmax of the first mold to (Tg+40)°C to (Tg+70)°C, and setting the temperature of the second mold to (Tmax-90)°C to (Tmax-65)°C.

2. The method for producing a plate-shaped molded product according to claim 1, wherein: The methacrylic resin composition has a tensile elongation at break of 1.2% or more.

3. The method for producing a plate-shaped molded product according to claim 1 or 2, wherein: After the first mold is heated, it is cooled to set the minimum temperature Tmin of the first mold to (Tg-75)°C to (Tg-45)°C.

4. The method for producing a plate-shaped molded product according to claim 1 or 2, wherein: After the first mold is heated, when cooling is performed, the temperature increase rate of the surface temperature of the first mold is set to 1 to 10° C. / second, and the temperature decrease rate is set to 0.5 to 10° C. / second.

Citation Information

Patent Citations

  • Multiilayered polymeric composition

    JP1976129449A

  • Multiilayered polymer compositions

    JP1977056150A

  • Production of impact-resistant acrylic polymer

    JP1984202213A

  • The multilayer structure of the method of manufacturing the acrylic resin molding material

    JP1985017406B2

  • Highly weather-and impact-resistant acrylic resin granular composite material

    JP1988027516A